Tire tread
The tire tread formulation with elastomers and fillers addresses the challenge of balancing strength, rolling resistance, and heat generation, resulting in improved fuel efficiency and performance.
Patent Information
- Application Number
- JP2024170843
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-06-05
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-09
AI Technical Summary
Existing tire designs face challenges in achieving a balance between excellent material strength, low rolling resistance, and low heat generation to meet fuel economy targets.
The tire tread is formulated with specific compositions of elastomers and fillers, including carbon black, to achieve desired properties such as elastic modulus ratio, percent elongation at break, and loss tangent, while ensuring effective filler dispersion through controlled mixing processes.
The formulation results in tire treads with improved material strength, low rolling resistance, and reduced heat generation, enhancing fuel efficiency and tire performance.
Smart Images

Figure 2025003449000001 
Figure 2025003449000002 
Figure 2025003449000003
Abstract
Description
[Technical field]
[0001] The present invention is directed to a tire tread and a tire. The tire tread and / or the tire preferably have improved material properties, such as, but not limited to, elastic modulus ratio, percent elongation at break, and / or loss tangent. The tire tread and the tire include an elastomeric material and a well-dispersed reinforcing filler. The tire can be a pneumatic tire with radial carcass reinforcement and an additional layer or zone of elastomeric material, intended to be mounted on vehicles that carry heavy loads and operate at sustained speeds, such as trucks, tractors, trailers, or buses. Alternatively, the tire and tire tread of the present invention can be fitted to other vehicles, including vehicles such as light trucks, passenger cars, high-performance cars, motorcycles, off-road vehicles, construction equipment vehicles, aircraft, and road-fitted vehicles with a rubber tread that is mounted on the road. [Background technology]
[0002] In heavy duty tires used for trucks and buses, as well as in other tire types, it is known to make tire treads of a multi-layer structure, such as a cap rubber layer that provides the outer surface of the tread and a base rubber layer that is radially disposed inside the cap rubber layer, with rubber having excellent wear resistance being used in the cap rubber layer and low heat build-up rubber having low loss tangent being used in the base rubber layer. In other higher stress areas of the tire, such as the shoulder areas of the tread, selected rubber compounds having improved properties are used. See, for example, U.S. Pat. No. 10,399,386. It is desirable to produce tire treads that simultaneously achieve high levels of wear and stress resistance, low heat build-up (low loss tangent), and low rolling resistance, thereby achieving improved fuel economy along with improved tire life and durability over the original replacement tire tread.
[0003] Many tire and tread designs and formulations have been proposed to balance the rubber material properties of mechanical and tensile strength against heat generation, e.g., vehicle weight and speed, surface conditions, and operating temperatures, to obtain acceptable tire performance and life under typical stresses. See, for example, U.S. Pat. Nos. 6,247,512, 10,479,037, 10,308,073, and U.S. Patent Application Publication No. 2009 / 0255613. Some have proposed using axially different materials to form the tread. The central equatorial plane material may be different from the lateral planar materials, and these materials may be different from the materials used in the various inner zones of the tread. See, for example, U.S. Pat. No. 9,713,942. In many cases, the outer material in contact with the ground exhibits better wear performance, and the inner material exhibits hysteresis properties that allow less heat generation and lower operating temperatures in the crown area when these materials are superimposed on the trend. The void pattern in the tread can be varied axially, often with a lower void ratio at the central equatorial plane and a higher groove or sipe surface area at the outer axial portion of the tread. Additional inner layers of elastomeric material have been proposed for targeted areas of mechanical strength and thermal management, with the thickness of each material layer selected to optimize tire life and performance. To improve tire performance metrics, some designs and formulations have identified elastomeric materials with improved filler dispersion levels achieved by the liquid elastomer masterbatch process as a means to optimize tire performance. See, for example, U.S. Pat. Nos. 10,308,073 B2, 10,017,612, 9,834,658, and 9,713,942 B2. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention preferably provides a tire that has both excellent material strength and sufficiently low rolling resistance, as well as low heat buildup to meet fuel economy targets.
[0005] It is a feature of the present invention to provide a tire tread having one or more advantageous properties.
[0006] A further feature of the present invention is to provide a tire tread that provides excellent material strength and / or sufficiently low rolling resistance and / or low heat build-up to meet fuel economy goals. [Means for solving the problem]
[0007] To achieve these and other advantages, and in accordance with the purpose of the present invention, as embodied and described herein, the present invention provides a tire tread comprising at least one elastomer and 40 to 80 phr of at least one filler, the filler comprising at least 40 phr of at least one carbon black, the tire tread comprising: a) Elastic modulus ratio > 5.60; b) Percent elongation at break >470; and c) Loss tangent at 60°C (333.15K) ≧ 0.10 and < 0.25 The tire tread has the following structure:
[0008] The present invention relates to a tire tread comprising at least one elastomer and 20 to 80 phr of at least one filler, the filler comprising up to 40 phr of at least one carbon black, the tread comprising: a) Elastic modulus ratio ≥ 5.43; b) Percent elongation at break >400; and c) Loss tangent at 60°C (333.15K) ≧0.09 and <0.15 The present invention further relates to the tire tread as described above,
[0009] Furthermore, the present invention relates to a tire tread comprising at least one elastomer and at least one filler in an amount of 20 to 80 phr, wherein the filler comprises at least one carbon black, and the tread is characterized by a macrodispersion value V, which is the percentage area of carbon black particles larger than 10 μm that are undispersed as determined by optical microscopy in transmission mode, and which satisfies the formula 0.01 < V < 0.15.
[0010] In addition, the present invention relates to a tire tread comprising at least one elastomer and at least one filler in an amount of 20 to 80 phr, wherein the filler comprises at least one carbon black, and the tread is characterized in that the macrodispersion value V, which is the percentage area of carbon black particles larger than 10 μm that are undispersed as determined by optical microscopy in transmission mode, is greater than 0.01, and the tread: a) has an elastic modulus ratio ≧ 5.43; or b) has a percent elongation at break > 400, or c) has a loss tangent at 60 °C (333.15 K) < 0.25 and has at least one of the above properties.
[0011] Furthermore, the present invention relates to a tire tread comprising at least one elastomer and at least one filler in an amount of 20 to 80 phr, wherein the filler comprises at least 40 phr of at least one carbon black, and the tire tread: a) has an elastic modulus ratio > 5.60; b) has a percent elongation at break > 400, and c) has a loss tangent at 60 °C (333.15 K) > 0.09 and < 0.15, and the tread is characterized by a macrodispersion value V, which is the percentage area of carbon black particles larger than 10 μm that are undispersed as determined by optical microscopy in transmission mode, and which satisfies the formula 0.01 < V < 0.15.
[0012] The present invention further relates to a tire tread which may comprise at least one elastomer and from 20 to 80 phr of at least one filler. The filler may comprise at least 40 phr of at least one carbon black. The tire tread comprises: a) Elastic modulus ratio > 5.60; b) percent elongation at break >480, and optionally c) Loss tangent at 60℃ (333.15K) < 0.25 may have: The tire tread is further characterized by a macrodispersion value V, the area percentage of undispersed carbon black particles larger than 10 μm, greater than 0.01, as determined by optical microscopy in transmission mode.
[0013] The present invention also relates to a tire comprising the tire tread of the present invention.
[0014] Additional features and advantages of the invention will be set forth in part in the detailed description which follows, and in part will be obvious from the detailed description, or may be learned by the practice of the invention. The objectives and other advantages of the invention will be realized and attained by means of the elements and combinations particularly pointed out in the detailed description and the appended claims.
[0015] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are intended to provide further explanation of the invention as claimed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The tire and tire tread of the present invention comprises a composite compounded with a rubber compound selected for the desired tire size, grade, and purpose. In one aspect of the present invention, the tire tread of the present invention can be characterized by an improved combination of material strength, low heat build-up, and low rolling resistance, as shown by the increased elastic modulus ratio and elongation at break, which is unexpectedly associated with a reduction in hysteresis (loss tangent). The tire tread of the present invention can be used in tires for heavy vehicles, such as tires used off-road, tires for agricultural vehicles and trucks, and buses, tires for lighter vehicles, such as light trucks, passenger cars, high performance cars, and motorcycles, tires for aircraft, and other tires on road-fitted vehicles having a rubber tread that is mounted on the road.
[0017] Various tire treads form part of the present invention and may be characterized by the phr amount of filler, the phr amount of carbon black that is part of the filler, the elastic modulus ratio value or range, the percent elongation at break value or range, the loss tangent value or range, and / or the macrodispersion value or range, and any combination of any two or more of these parameters as further described herein.
[0018] For example, a tire tread of the invention may comprise at least one elastomer and 40 to 80 phr of at least one filler (Tire Tread A). The filler may comprise at least 40 phr of at least one carbon black. The tire tread may comprise: a) Elastic modulus ratio > 5.60; b) Percent elongation at break >470; and c) Loss tangent at 60°C (333.15K) ≧ 0.10 and < 0.25 may have:
[0019] For tire treads generally, and for tire tread A, the values of modulus ratio, percent elongation at break, and loss tangent can be based on tests where the tire tread tested has carbon black present at 50 phr.
[0020] With respect to the tire tread generally, and to tire tread A, the elastic modulus ratio can be, for example, 5.61 or more, 5.62 or more, 5.63 or more, 5.64 or more, 5.65 or more, 5.65 or more, 5.66 or more, 5.67 or more, 5.68 or more, 5.69 or more, 5.7 or more, 5.71 or more, 5.75 or more, such as 5.61 to 6.3, or 5.62 to 6.3, or 5.63 to 6.3, or 5.67 to 6.3, or 5.7 to 6.3, or other values within one of these ranges.
[0021] For the tire tread generally, and for tire tread A, the percent elongation at break can be 471 or more, 472 or more, 473 or more, 474 or more, 475 or more, 480 or more, 485 or more, 490 or more, 495 or more, 500 or more, for example, 475-550, or 480-525, or 480-500, or other values within one of these ranges.
[0022] For the tire tread in general, and for tire tread A, the loss tangent may be 0.10 to 0.249, or 0.10 to 0.245, or 0.10 to 0.24, or 0.10 to 0.23, or 0.10 to 0.22, or 0.11 to 0.245, or 0.11 to 0.24, or 0.12 to 0.2, or any other value within one of these ranges.
[0023] With respect to the tire tread generally, and tire tread A, the elastomer may include natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, or any blend thereof, or the elastomer may be any of the elastomers or blends thereof as described herein and in further detail below.
[0024] The present invention further relates to a tire tread (Tire Tread B) which may comprise at least one elastomer and from 20 to 80 phr of at least one filler. The filler may comprise up to 40 phr of at least one carbon black. The tire tread comprises: a) Elastic modulus ratio ≥ 5.43; b) Percent elongation at break >400; and c) Loss tangent at 60°C (333.15K) > 0.09 and < 0.15 may have:
[0025] For tire tread B in general, and tire tread B, the values of modulus ratio, percent elongation at break, and loss tangent can be based on a tire tread tested with a carbon black load of 40 phr.
[0026] For tire tread B generally, and tire tread B, the elastic modulus ratio can be 5.43 or greater, 5.5 or greater, 5.6 or greater, 5.7 or greater, 5.8 or greater, 5.9 or greater, 6.0 or greater, for example, 5.43 to 6.25, or 5.43 to 6.2, or any value within a range therein.
[0027] For tire treads generally, and tire treads B, the percent elongation at break can be 401 or more, 402 or more, 403 or more, 404 or more, 405 or more, 410 or more, 415 or more, 420 or more, 425 or more, 430 or more, 435 or more, 440 or more, 445 or more, 450 or more, 455 or more, 460 or more, 465 or more, 470 or more, 475 or more, 480 or more, 485 or more, 490 or more, 495 or more, 500 or more, for example, 405-550, or 425-525, or 425-500, or any value within one of these ranges.
[0028] Generally regarding the tire tread and tire tread B, the loss tangent can be 0.091 to 0.149, or 0.091 to 0.145, or 0.091 to 0.14, or 0.092 to 0.14, or 0.095 to 0.13, or 0.095 to 0.14, or 0.10 to 0.12, or 0.10 to 0.11, or any value within one of these ranges.
[0029] Generally regarding the tire tread as well as tire treads A and / or B, the tire tread can be further characterized by the macrodispersion value V. This value V is the area percentage of undispersed carbon black particles exceeding 10 μm, which is determined by an optical microscope in the transmission mode. The macrodispersion value V can be according to the formula: 0.01 < V < 0.15. The macrodispersion value V can be 0.011 < V < 0.15, or 0.012 < V < 0.15, or 0.013 < V < 0.15, or 0.014 < V < 0.15, or 0.015 < V < 0.15, or 0.02 < V < 0.15, or 0.05 < V < 0.15, or 0.07 < V < 0.15, or 0.08 < V < 0.15, or 0.09 < V < 0.12, or any value within one of these ranges.
[0030] The present invention further relates to a tire tread (tire tread C) that may include at least one elastomer and at least one filler of 20 to 80 phr. The filler may include at least one carbon black. The tire tread may be characterized by the above-mentioned macrodispersion value V, which is the area percentage of carbon black particles not dispersed exceeding 10 μm, determined by an optical microscope in the transmission mode. The macrodispersion value V may be according to the formula: 0.01 < V < 0.15. The macrodispersion value V may be 0.011 < V < 0.15, or 0.012 < V < 0.15, or 0.013 < V < 0.15, or 0.014 < V < 0.15, or 0.015 < V < 0.15, or 0.016 < V < 0.15, or 0.017 < V < 0.15, or 0.018 < V < 0.15, or 0.019 < V < 0.15, or 0.02 < V < 0.15, or 0.05 < V < 0.15, or 0.07 < V < 0.15, or 0.08 < V < 0.15, or 0.09 < V < 0.14, or 0.01 < V < 0.13, or 0.01 < V < 0.12, or 0.01 < V < 0.11, or 0.01 < V < 0.1, or any value within one of these ranges.
[0031] For any of the macrodispersion values V, V can be based on a test where the tire tread being tested has a carbon black content of 50 phr.
[0032] The present invention further relates to a tire tread (tire tread D) that may include at least one elastomer and at least one filler of 20 to 80 phr. The filler may include at least one carbon black of 40 phr or less. The tread may be characterized in that the macrodispersion value V (the area percentage of carbon black particles not dispersed exceeding 10 μm, determined by an optical microscope in the transmission mode) is greater than 0.01, as described above. The tire tread may be one or more of the following (or two or all three of the following): a) Elastic modulus ratio ≧ 5.43; or b) Percent elongation at break > 400, or c) Loss tangent at 60 °C (333.15 K) < 0.25 may have.
[0033] Generally with respect to the tire tread and tire tread D, the tire tread may have values of modulus ratio, percent elongation at break, and loss tangent based on a test in which the tire tread being tested has carbon black in an amount of 40 phr.
[0034] Generally with respect to the tire tread and tire tread D, the macrodispersion value V is 0.011 or more, 0.012 or more, 0.013 or more, more than 0.014, or more than 0.015, or more than 0.016, or more than 0.017, or more than 0.02, or more than 0.03, or more than 0.05, or more than 0.1, or more than 0.11, or more than 0.12, or more than 0.13, or more than 0.14, or 0.011 < V < 0.14, or 0.012 < V < 0.13, or 0.01 < V < 0.14, or 0.015 < V < 0.14, or 0.02 < V < 0.13, or 0.05 < V < 0.12, or 0.07 < V < 0.11, or 0.01 < V < 0.1, or 0.01 < V < 0.09, or any value within one of these ranges may be possible.
[0035] Generally with respect to the tire tread and tire tread D, the modulus ratio is 5.43 or more, more than 5.45, or more than 5.5, or more than 5.6, or more than 5.7, or more than 5.8, or more than 5.9, or more than 5.9, for example, 5.43 to 6.25, or 5.43 to 6.5, or 5.43 to 6.5, or 5.45 to 6.5, or 5.00 to 6.2, or any value between any one of these ranges may be possible.
[0036] For the tire tread generally, and for tire tread D, the percent elongation at break can be 401 or more, 402 or more, 403 or more, 404 or more, 405 or more, 410 or more, 415 or more, 420 or more, 425 or more, 430 or more, 435 or more, 440 or more, 445 or more, 450 or more, 455 or more, 460 or more, 465 or more, 470 or more, 475 or more, 480 or more, 485 or more, 490 or more, 495 or more, 500 or more, for example, 405-550, or 425-525, or 425-500, or any value within one of these ranges.
[0037] For tire treads in general, and tire tread D, the loss tangent can be 0.249 or less, or 0.245 or less, or 0.24 or less, or less than 0.24, or less than 0.23, or less than 0.22, or less than 0.21, or less than 0.2, or less than 0.18, or less than 0.16, or less than 0.14, or less than 0.12, or less than 0.1, for example, 0.09 to 0.249, or 0.09 to 0.245, or 0.09 to 0.22, or 0.10 to 0.2, or any value between any one of these ranges.
[0038] The present invention further relates to a tire tread (Tire Tread E) which may comprise at least one elastomer and 40 to 80 phr of at least one filler. The filler may comprise at least 40 phr of at least one carbon black. The tire tread may have a modulus ratio > 5.60, a percent elongation at break > 470, and a loss tangent at 60°C (333.15K) > 0.10 and < 0.25.
[0039] For tire treads generally, and tire tread E, the elastic modulus ratio can be greater than 5.61, or greater than 5.62, or greater than 5.65, or greater than 5.7, or greater than 5.8, or greater than 5.9, or greater than 6, or greater than 6.1, or greater than 6.2, for example, 5.61 to 6.2, or 5.65 to 6.1, or 5.7 to 6, or any value between any one of these ranges.
[0040] For the tire tread generally, and for tire tread E, the percent elongation at break can be 471 or more, 472 or more, 473 or more, 474 or more, 475 or more, 480 or more, 485 or more, 490 or more, 495 or more, 500 or more, for example, 475-550, or 480-525, or 480-500, or other values within one of these ranges.
[0041] For the tire tread in general, and for tire tread E, the loss tangent at 60° C. (333.15 K) may be 0.101 to 0.249, or 0.105 to 0.245, 0.11 to 0.24, 0.12 to 0.24, 0.13 to 0.24, or 0.14 to 0.24, or 0.15 to 0.24, or 0.16 to 0.23, or 0.17 to 0.23, or 0.18 to 0.22, or any other value within one of these ranges.
[0042] The invention further relates to a tire tread (tire tread F) which may comprise at least one elastomer and from 20 to 80 phr of at least one filler. The filler may comprise at least 40 phr of at least one carbon black. The tire tread comprises: a) Elastic modulus ratio > 5.60; b) percent elongation at break >480, and optionally c) Loss tangent at 60℃ (333.15K) < 0.25 may have: For tire tread F, the loss tangent parameter is optional. Furthermore, generally, for tire tread F, the tire tread may be characterized by a macrodispersion value V (area percentage of undispersed carbon black particles larger than 10 μm, as determined by optical microscopy in transmission mode) greater than 0.01, as previously described.
[0043] With respect to the tire tread generally, and tire tread F, the tire tread may have values for modulus ratio, percent elongation at break, and loss tangent based on tests in which the tire tread tested had carbon black in an amount of 50 phr.
[0044] For the tire tread generally, and for tire tread F, the elastic modulus ratio can be 5.61 or more, 5.62 or more, 5.63 or more, 5.64 or more, 5.65 or more, 5.66 or more, 5.67 or more, 5.68 or more, 5.69 or more, 5.7 or more, greater than 5.8, or greater than 5.9, or greater than 6.0, or greater than 6.1, or greater than 6.2, or greater than 5.65, or greater than 5.75, for example, 5.61 to 6.25, or 5.65 to 6.5, or 5.63 to 6.2, or any value between any one of these ranges.
[0045] For the tire tread generally, and for tire tread F, the percent elongation at break can be 481 or more, 482 or more, 483 or more, 484 or more, 485 or more, 490 or more, 495 or more, 500 or more, 505 or more, 510 or more, for example, 481 to 550, or 485 to 525, or 490 to 500, or any other value within one of these ranges.
[0046] Generally, for the tire tread, and for the tire tread F, the loss tangent is less than 0.25, or less than 0.24, or less than 0.23, or less than 0.22, or less than 0.21, or less than 0.2, or less than 0.19, or less than 0.18, or less than 0.17, or less than 0.16, or less than 0.15, for example, from 0.09 to 0.249, or from 0.09 to 0.24, or from 0.09 to 0.23, or from 0.09 to 0.22, or ..., or from 0.09 to 0.22, or from 0.09 to 0.24, or from 0.09 to 0.24, or from 0.09 to 0.22, or from 0.09 to 0.24, or from 0.09 to 0.24, or from 0. It may be greater than 0.09 and less than 0.24, or greater than 0.1 and less than 0.24, or 0.1 to 0.24, or 0.1 to 0.23, or 0.11 to 0.23, 0.09 to 0.145, or 0.095 to 0.14, or 0.095 to 0.13, or 0.11 to 0.14, or 0.09 to 0.13, or 0.09 to 0.12, or 0.10 to 0.14, or 0.10 to 0.13, or any value between any one of these ranges.
[0047] For the tire tread in general, and for the tire tread F, the macrodispersion value V is between 0.011 and 0.149, or between 0.012 and 0.145, or between 0.014 and 0.145, between 0.015 and 0.14, between 0.02 and 0.14, between 0.03 and 0.14, between 0.04 and 0.14, between 0.03 and 0.06, between 0.02 and 0.12, between 0.02 and 0.11, between 0.02 and 0.1, between 0.02 and 0.09, between 0.02 and 0.08, between 0.02 and 0. The molecular weight may be 0.07, 0.02 to 0.06, 0.011 to 0.099, more than 0.01 and less than 0.1, 0.011 to 0.099, or 0.012 to 0.095, or 0.012 to 0.09, or 0.015 to 0.09, or 0.02 to 0.09, or 0.02 to 0.085, or 0.02 to 0.08, or 0.025 to 0.07, or any value between any one of these ranges.
[0048] For any of the tire treads, including any one of tire treads A-F, the filler can include at least one material selected from carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof, or any combination thereof.
[0049] For any of the tire treads, including any one of tire treads A through F, the filler can comprise carbon black and silica in a carbon black to silica weight ratio of greater than 2.7:1, or greater than 2.8:1, or greater than 2.9:1, or greater than 3:1, or greater than 3.5:1, or greater than 4:1, or greater than 4.5:1, or greater than 5:1, for example, from 2.75:1 to 10:1, or other weight ratios within any one of these ranges.
[0050] For any of the tire treads, including any one of tire treads A-F, the elastomer may be selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, or any blend of two or more thereof.
[0051] For any of the tire treads, including any one of tire treads A-F, the tire tread can further include one or more rubber chemicals selected from antidegradants, processing aids and activators, zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and / or processing oils, any one or more of which may be present.
[0052] For any of the tire treads, including any one of tire treads A through F, the tire tread may have carbon black present as a filler or one of the fillers. The carbon black may have a STSA of >140m. 2 / g, or STSA>150m 2 / g, or 110m 2 / g~220m 2 / g STSA or 120m 2 / g~180m 2 / g STSA or 140m 2 / g~180m 2 / g STSA or 150m 2 / g~160m 2 / g. Further details of the fillers, including carbon black, are provided below and may be used in any of the tire tread formulations.
[0053] The tire tread of the present invention may be formed by utilizing one or more of the following process steps to form an elastomer composite which may then be incorporated into a tire tread formulation to produce the tire tread. The present invention includes any tire tread and / or tire formed by any one of the processes described herein or any combination thereof.
[0054] Process step (1) may be used to make the tire tread of the present invention as follows: (a) charging into a mixer materials including one or more solid elastomer(s) and one or more wet filler(s) including at least 15% by weight liquid based on the weight of the filler(s) and the total wet filler(s); (b) mixing the charged materials to form a mixture at a mixer temperature controlled by at least one temperature control means, optionally with such control means set at a temperature Tz in the range of 30°C (303.15K) to 150°C (423.15K), and at a mixer rotor tip speed of at least 0.6 m / s for at least 50% of the duration of mixing, while removing at least a portion of the liquid, optionally at least 50% by weight of the liquid, from the mixture by evaporation; and (c) discharging from the mixer an elastomer composite having a filler(s) dispersed in the elastomer(s) at a charge of at least 20 phr with no more than a 10% filler yield loss, the composite having a liquid content of no more than 10% by weight based on the total elastomer composite weight.
[0055] Process step (2) may be used to make the tire tread of the present invention as follows: (a) charging into a first mixer materials including one or more solid elastomer(s) and one or more wet filler(s) including at least 15% liquid by weight based on the weight of the filler(s) and the total wet filler(s); (b) mixing the materials in one or more mixing steps to form a mixture, and in at least one of said mixing steps, performing said mixing at a mixer rotor tip speed of at least 0.6 m / s for at least 50% of the duration of mixing while removing at least a portion of the liquid, optionally at least 50% by weight of the liquid, from the mixture by evaporation; (c) discharging a mixture from the first mixer, the mixture including at least 20 phr of filler(s) dispersed in the elastomer(s), the mixture having a liquid content reduced to an amount less than an initial liquid content, and the mixture having a material temperature in the range of 100°C (373.15K) to 180°C (453.15K); (d) charging and mixing the mixture from (c) into a second mixer to obtain an elastomeric composite, the second mixer being operated under at least one of the following conditions: (i) 5 psi (3.448275 × 10 -2 Ram pressure below 1 Pa; (ii) rum elevated to at least 75% of its highest level; (iii) A ram operated in floating configuration; (iv) a ram positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and / or (vi) The fill factor of the mixture is in the range of 25% to 70%; and (e) discharging the elastomeric composite from the second mixer having a liquid content of less than 3 weight percent based on the total elastomeric composite weight.
[0056] A more detailed example of a process that may be used or included in making the tire tread of the present invention may be as follows.
[0057] One method of making a tire tread of the present invention may include: (a) providing a wet-mixed composite, said wet-mixed composite being prepared by: (i) introducing into a mixer having one or more rotors a wet filler comprising at least a solid elastomer and a liquid present in an amount ranging from 15% to 65% by weight based on the total weight of the filler and the wet filler; (ii) mixing at least a solid elastomer and a wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is performed, the mixer having at least one temperature control means set at a temperature Tz equal to or greater than 65°C (338.15K), and removing at least a portion of the liquid from the mixture by evaporation; and (iii) discharging from the mixer a wet mixed composite comprising a filler dispersed in an elastomer at a charge of at least 20 phr with a filler yield loss of not more than 10%, the wet mixed composite having a liquid content of not more than 5% by weight based on the total weight of said composite; (b) incorporating the wet mix composite into a tire tread compound in at least one mixing stage; and (c) Fabricating a tire tread from the tire tread compound.
[0058] Another method of making a tire tread of the present invention may include: (a) providing a wet-mixed composite, said wet-mixed composite being prepared by: (i) introducing into a mixer at least a solid elastomer comprising at least 50% by weight of natural rubber, and a wet filler comprising filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; wherein the at least solid elastomer and the wet filler have a fill factor of 68% or less on a dry weight basis; (ii) mixing at least a solid elastomer and a wet particulate filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, performing said mixing at a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation; (iii) discharging a composite comprising a filler dispersed in an elastomer at a charge of at least 20 phr from the mixer with a filler yield loss of not more than 10%, the composite having a liquid content of not more than 10% by weight based on the total weight of said composite; (b) incorporating the wet mix composite into a tire tread compound in at least one mixing stage; and (c) Fabricating a tire tread from the tire tread compound.
[0059] A further method of making a tire tread of the present invention may include: (a) providing a wet-mixed composite, said wet-mixed composite being prepared by: (i) introducing into a mixer a wet filler comprising at least a solid elastomer, and a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; (ii) mixing at least a solid elastomer and a wet filler in one or more mixing steps to form a mixture, and, in at least one of said mixing steps, said mixing is performed with one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, at a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation; and (iii) discharging a wet mixed composite comprising a filler dispersed in an elastomer at a charge of at least 20 phr from the mixer with a filler yield loss of not more than 10%, the wet mixed composite having a liquid content of not more than 10% by weight based on the total weight of said wet mixed composite; (b) incorporating the wet mix composite into a tire tread compound in at least one mixing stage; and (c) Fabricating a tire tread from the tire tread compound.
[0060] Yet a further method of making a tire tread of the present invention may include: (a) providing a wet-mixed composite, said wet-mixed composite being prepared by: (i) introducing a wet filler, the wet filler including at least a solid elastomer, and a liquid present in an amount of at least 15% by weight, based on the total weight of the wet filler, into a first mixer having one or more rotors; (ii) mixing at least a solid elastomer and a wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is performed with one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, at a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation; (iii) discharging a mixture from a first mixer, the mixture including a filler dispersed in an elastomer at a charge of at least 20 phr, the mixture having a liquid content in the range of 1% to 20% by weight based on a total weight of the composite, the mixture having a material temperature in the range of 100° C. (373.15 K) to 180° C. (453.15 K); (iv) mixing the mixture from (iii) in a second mixer to obtain a composite, the second mixer being operated under at least one of the following conditions: -5psi (3.448275 x 10 -2 Ram pressure below 1 Pa; -Rum raised to at least 75% of its maximum level; -ram operated in floating form; - a ram positioned so as not to substantially contact the mixture; - the mixer is ramless; and / or - the fill factor of the mixture is in the range of 25% to 70%; and (v) discharging the wet mixed composite from the second mixer having a liquid content of less than 3% by weight based on the total weight of the wet mixed composite; (b) incorporating the wet mix composite into a tire tread compound in at least one mixing stage; and (c) Fabricating a tire tread from the tire tread compound.
[0061] A further method of making a tire tread of the present invention may include: (a) providing a wet-mixed composite, said wet-mixed composite being prepared by: (i) introducing a wet filler, the wet filler including at least a solid elastomer, and a liquid present in an amount of at least 15% by weight, based on the total weight of the wet filler, into a first mixer having one or more rotors; (ii) mixing at least a solid elastomer and a wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, performing said mixing with a mixer temperature controlled by at least one temperature control means and applying an average specific power of at least 2.5 kW / kg over the mixing time, and removing at least a portion of the liquid from the mixture by evaporation; (iii) discharging a mixture from the first mixer, the mixture comprising the filler dispersed in the elastomer at a charge of at least 20 phr, the mixture having a liquid content reduced to an amount less than the liquid content at the beginning of step (ii), the mixture having a material temperature in the range of 100°C (373.15K) to 180°C (453.15K); (iv) mixing the mixture from (iii) in a second mixer to obtain a composite, the second mixer being operated under at least one of the following conditions: -5psi (3.448275 x 10 -2 Ram pressure below 1 Pa; -Rum raised to at least 75% of its maximum level; -ram operated in floating form; - a ram positioned so as not to substantially contact the mixture; - the mixer is ramless; and / or - the fill factor of the mixture is in the range of 25% to 70%; and (v) discharging the composite from the second mixer having a liquid content of less than 3% by weight, based on the total weight of the composite; (b) incorporating the wet mix composite into a tire tread compound in at least one mixing stage; and (c) Fabricating a tire tread from the tire tread compound.
[0062] Additionally, as used herein, the term "wet mixed composite" refers to an elastomeric composite material made from a solid elastomer and a wet filler by optional further processing steps in combination with process step (1) or process step (2) or any set of other processes described herein. The further processing steps include, but are not limited to, the following: (a) at least 50% by weight, or at least 40% by weight, of the filler comprises carbon black material; and / or the carbon black material is dispersed in the elastomer(s) at a charge of 30 to 150 phr; and / or the carbon black material is dispersed in the elastomer(s) at a charge of 60 m 2 / g~200m 2 Selection of a filler having a STSA in the range of 100 mL / 100 g and / or a COAN in the range of 60 mL / 100 g to 120 mL / 100 g; (b) selecting a liquid that is volatile at the elastomer composite mixing temperature; and / or selecting a liquid that includes water; and / or selecting a liquid that includes components selected from acids, bases, salts, surfactants, and processing aids; (c) selecting mixer conditions to obtain a total specific energy for mixing the elastomeric composite of at least 1,400 KJ / Kg; and / or applying energy to the mixer to obtain a time-average discharge rate of liquid of 0.01 to 0.14 kg / (min·kg), based on kg dry weight of the elastomeric composite; and / or a liquid content of the discharged elastomeric composite of 5% by weight or less, based on the total weight of the elastomeric composite; (d) Selection of batch, semi-continuous and / or continuous mixers and mixing processes; and / or excluding one or more rubber chemicals and discharged elastomer composites from the mixing process; and / or applying a pressure of 5 psi (3.448275 x 10 -2operation of the second mixer at a ram pressure of 0.1 Pa or less and / or at a temperature Tz in the range of 60°C (333.15 K) to 110°C (383.15 K), or in the range of 65°C (338.15 K) to 100°C (373.15 K), or in the range of 50°C (323.15 K) to 100°C (373.15 K); and / or operation of the first mixer at a fill factor of 50 to 70%; and / or (e) Selection of a mixer as the second mixer operated under at least one of the following conditions: (i) 5 psi (3.448275 × 10 -2 Ram pressure below 1 Pa; (ii) rum elevated to at least 75% of its highest level; (iii) A ram operated in floating configuration; (iv) a ram positioned so as not to substantially contact the mixture; (v) the mixer is ramless; and / or (vi) The fill factor of the mixture is in the range of 25% to 70%.
[0063] Additionally, as used herein, the term "wet mixed composite" refers to any elastomeric composite material made from a solid elastomer and a wet filler by any of the processes disclosed in U.S. Provisional Patent Application No. 62 / 857,779 and PCT Application No. PCT / US20 / 36168, entitled "METHODS OF PREPARING A COMPOSITE HAVING ELASTOMER AND FILLER," which are incorporated herein by reference.
[0064] In the detailed description of the present invention, the terms "rubber" and "elastomer" are used interchangeably unless otherwise specified. The terms "rubber composition", "compound", "compounded rubber", and "rubber compound" as used herein are used interchangeably to refer to "rubber blended or mixed with various ingredients", and the term "compound" refers to "rubber composition" unless otherwise indicated. Such terms are well known to those skilled in the art of rubber mixing or rubber compounding. The term "phr" refers to parts of each material per 100 parts of rubber or elastomer on a dry weight basis. The terms "cured" and "vulcanized" or "vulcanizate" are used interchangeably with respect to crosslinked rubber compounds in tires, unless otherwise indicated.
[0065] The tire tread of the present invention is characterized by excellent filler dispersion. Filler dispersion can be measured in cured or vulcanized rubber compounds by a technique using an optical microscope in transmission mode to determine the macrodispersion value "V", which represents the area percentage of undispersed carbon black particles larger than 10 μm. Such composites have unique product properties. The tire tread of the present invention, comprising at least one elastomer and 20 to 80 phr of at least one filler, wherein the filler comprises at least one carbon black, can be characterized by the macrodispersion value V, the elastic modulus ratio, the percent elongation at break, or the loss tangent at 60° C. (333.15 K), determined by typical industrial test methods described in the following examples.
[0066] Solid Elastomer Solid elastomers useful in the wet-filler composite can include, but are not limited to, any solid form of natural or synthetic elastomer suitable for use in tire components or tire treads.
[0067] Optionally, the solid elastomer used in the composite of the present invention may be at least one of natural rubber and its treated and functionalized derivatives. For example, natural rubber may be treated to chemically or enzymatically modify or reduce various non-rubber components, or the rubber molecule itself may be modified with various monomers or other chemical groups, such as chlorine. Optionally, epoxidized natural rubber may be used, as described in PCT Publication WO 2017 / 207912, where the natural rubber has a nitrogen content of up to 0.3% by weight. Technical descriptions of natural rubber useful herein are widely available, for example, in Rubber World Magazine's Blue Book, published by Lippincott and Peto, Inc. (Akron, Ohio, USA). The solid elastomer used in the composites of the present invention can be at least one elastomer selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and blends thereof.
[0068] Exemplary elastomers include, but are not limited to, rubbers, polymers (e.g., homopolymers, copolymers, and / or terpolymers) of 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadiene, where the alkyl can be methyl, ethyl, propyl, etc., acrylonitrile, ethylene, propylene, etc. The elastomers may have a glass transition temperature (Tg) ranging from about -120°C (153.15K) to about 0°C (273.15K) as measured by differential scanning calorimetry (DSC). Examples include, but are not limited to, styrene-butadiene rubber (SBR), natural rubber and its derivatives, such as chlorinated rubber, polybutadiene, polyisoprene, poly(styrene-co-butadiene), and oil-extended derivatives of any of these. Blends of any of the above may also be used. Particularly preferred synthetic rubbers include: copolymers of styrene and butadiene containing from about 10 weight percent to about 70 weight percent styrene and from about 90 to about 30 weight percent butadiene, such as 19 parts styrene and 81 parts butadiene, 30 parts styrene and 70 parts butadiene, 43 parts styrene and 57 parts butadiene, and 50 parts styrene and 50 parts butadiene; polymers and copolymers of conjugated dienes, such as polybutadiene, polyisoprene, polychloroprene, and the like; and copolymers of such conjugated dienes with ethylenically copolymerizable monomers, such as styrene, methylstyrene, chlorostyrene, acrylonitrile, 2-vinyl-pyridine, 5-methyl-2-vinylpyridine, 5-ethyl-2-vinylpyridine, 2-methyl-5-vinylpyridine, allyl-substituted acrylates, vinyl ketones, methyl isopropenyl ketone, methyl vinyl ether, alpha-methylene carboxylic acids and their esters and amides, such as acrylic acid and dialkylacrylic acid amides. Copolymers of ethylene with other higher alpha olefins, such as propylene, 1-butene, and 1-pentene, are also suitable for use herein.Other polymers are disclosed in US Patent Publication No. 2018 / 0282523 and EP Patent No. 2423253(B1), the disclosures of which are incorporated herein by reference. Other polymers include silicone-based elastomers or hybrid systems having silicone and hydrocarbon domains. With respect to the solid elastomers used and mixed with the wet filler, the solid elastomer can be a dry elastomer or a substantially dry elastomer. The solid elastomer has a moisture content (or water content) of 5% or less by weight, for example, 4% or less by weight, 3% or less by weight, 2% or less by weight, 1% or less by weight, or 0.1% to 5% by weight, 0.5% to 5% by weight, 1% to 5% by weight, 0.5% to 4% by weight, and the like, based on the total weight of the solid elastomer. The solid elastomer may be entirely elastomer (having a starting moisture content of 5% by weight or less), or may be a solid elastomer masterbatch that also includes one or more fillers and / or other ingredients. For example, the solid elastomer may be 50% to 99.9% by weight elastomer, on a dry weight basis, with 0.1% to 50% by weight of filler predispersed in the elastomer, the predispersed filler being in addition to the wet filler that is incorporated into the composite.
[0069] With respect to the solid elastomer masterbatch used and mixed with the wet filler, the solid elastomer masterbatch can be a dry elastomer masterbatch or a substantially dry elastomer masterbatch, the solid elastomer masterbatch having a moisture content (or water content) of 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, or 0.1% to 5%, 0.5% to 5%, 1% to 5%, 0.5% to 4% and the like.
[0070] A solid elastomer masterbatch (e.g., starting solid elastomer masterbatch) is an elastomer that includes one or more fillers and, optionally, other ingredients. For example, a solid elastomer masterbatch may include 1 phr to 100 phr of filler predispersed in the elastomer, or 20 phr to 80 phr of filler predispersed in the elastomer, or 30 phr to 70 phr of filler predispersed in the elastomer, or 40 phr to 60 phr of filler predispersed in the elastomer, and the like. Other ingredients, such as additional elastomers, antioxidants, and other rubber chemicals and additives, may be present in the solid elastomer in amounts of 0.1 phr to less than 50 phr. A solid elastomer masterbatch may contain any elastomer, any filler, any additive, and any combination thereof, in any amount as described and exemplified herein and known in the art. The total filler content in the finished rubber compound includes the added wet filler plus the filler predispersed in the solid elastomer masterbatch, which may be a dry and / or wet mixed composite, or a dry mix or compound made by a dry masterbatch process.
[0071] The second elastomeric material may be combined with the solid elastomer (or masterbatch) before, at the same time, or after the wet filler is combined with the solid elastomer (or masterbatch). The second elastomeric material may be at least one solid elastomer; at least one additional solid elastomer masterbatch. The second elastomeric material may comprise the same elastomer as the solid elastomer, or at least one different elastomer selected from one or more of the elastomers described herein or known in the art. The second elastomeric material may comprise at least one rubber chemical described herein or known in the art.
[0072] Filler In preparing the rubber compound for the tire tread of the present invention, a wet mix composite may be used. A wet mix composite utilizing a wet filler (e.g., including a filler and a liquid) allows batch times and temperatures to be controlled beyond those achievable in known dry mix processes, providing other benefits, such as improved filler dispersion and / or easier rubber-filler interaction and / or improved rubber compound performance. A wet filler may be effective when sufficient liquid is used to wet a substantial portion or substantially all of the filler surface prior to mixing with the solid elastomer. In general, as described herein, the mixing process may be managed by controlling one or more mixer or process parameters, such as mixer surface temperature and / or rotor speed, fill factor, incorporation of rubber chemicals (if present) at later times in the mix cycle, composite discharge temperature, and / or application of two or more mix stages.
[0073] The method for preparing a wet mixed composite includes introducing or introducing at least a solid elastomer and a wet filler, such as a) one or more solid elastomers and b) one or more fillers, into a rubber mixer, where at least one filler or at least a portion of the filler is wetted by a liquid (wet filler) before mixing with the solid elastomer. The solid elastomer and the wet filler are combined to form a mixture during a mixing step(s). The method further includes performing the above mixing in one or more mixing steps, where at least a portion of the liquid is removed by evaporation or an evaporation process performed during mixing. The liquid of the wet filler may be removed by evaporation (and at least a portion may be removed under the mixing conditions listed) and may be a volatile liquid, such as volatile at the bulk mixture temperature. For example, the boiling point of the liquid at 1 atm (101,325 Pa) may be 60°C (333.15K) to 110°C (383.15K), 60°C (333.15K) to 100°C (373.15K), 60°C (333.15K) to 90°C (363.15K), 90°C (363.15K) to 110°C (383.15K), 90°C (363.15K) to 100°C (373.15K), 95°C (368.15K) to 120°C (393.15K), or 95°C (368.15K) to 110°C (383.15K). For example, a volatile liquid may be distinguished from oils (e.g., extender oils, process oils) that may be present during at least a portion of the mixing, such that such oils are intended to be present in the expelled composite and therefore do not evaporate during a substantial portion of the mixing time.
[0074] With regard to the wet filler, in one embodiment, the wet filler has a solid consistency. Preferably, the dry filler is wetted only to the extent that the resulting wet filler maintains the form or similar consistency of a powder, particulate, pellet, cake, or paste, and / or has the appearance of a powder, particulate, pellet, cake, or paste. The wet filler does not flow like a liquid (e.g., at zero applied stress). Optionally, the wet filler, whether individual particles, agglomerates, pellets, cake, or paste, can maintain its shape at 25°C (298.15K) when molded into such shape. The wet filler is not a composite made by a liquid masterbatch process, nor any other pre-blended composite of filler dispersed in a solid elastomer where the elastomer is the continuous phase. In another embodiment, the wet filler can be a slurry. In yet another embodiment, the wet filler is not a slurry of filler and does not have the consistency of a liquid or slurry.
[0075] The filler, in the dry state, may contain a small amount of liquid (e.g., water) adsorbed on its surface. For example, carbon black may have a moisture content of 1-3% or 4% by weight, and precipitated silica may have a moisture content of 4-7% by weight. Such fillers are referred to herein as dry or non-wetting fillers. For the present wet fillers, additional liquid has been added to the filler and is present on the surface of the filler, including the interior surfaces or pores accessible to the liquid. During mixing, at least a portion of the liquid may be removed by evaporation as the wet filler is dispersed in the solid elastomer, and the surface of the filler may then be available to interact with the solid elastomer. The wet filler may have a liquid content of at least 20% by weight based on the total weight of the wet filler, for example at least 30%, at least 40%, at least 50% by weight based on the total weight of the wet filler, or between 20% and 80%, between 30% and 80%, between 30% and 70%, between 30% and 60%, between 40% and 80%, between 40% and 70%, between 40% and 60%.
[0076] The liquid used to wet the filler may be or include an aqueous liquid, such as, but not limited to, water. The liquid may include at least one other component, such as, but not limited to, base(s), acid(s), salt(s), solvent(s), surfactant(s), coupling agent(s), and / or processing aid(s), and / or any combination thereof.
[0077] Optionally, the mixture may further include one or more non-wetting fillers (e.g., any filler that is not wetted as described herein, e.g., a dry filler, e.g., a filler having 10% or less liquid by weight).
[0078] The filler used to make the wet filler composite can be any conventional filler used with elastomers, such as reinforcing fillers, including, but not limited to, carbon black, silica, fillers containing carbon black, fillers containing silica, and / or any combination thereof. The filler can be particulate or fibrous or plate-like. For example, particulate fillers are made of separate bodies. Such fillers can often have an aspect ratio (e.g., length to diameter) of 3:1 or less, or 2:1 or less, or 1.5:1 or less. Fibrous fillers can have an aspect ratio of, for example, 2:1 or more, 3:1 or more, 4:1 or more, or more. Typically, fillers used to reinforce elastomers have dimensions that are microscopic (e.g., hundreds of microns or less) or nanoscale (e.g., less than 1 micron). In the case of carbon black, separate particulate carbon black bodies refer to aggregates or agglomerates formed from primary particles and not the primary particles themselves. In other embodiments, the fillers can have plate-like structures, such as graphene and reduced graphene oxide.
[0079] The carbon black used in the tire tread of the present invention can be untreated or treated carbon black or a mixture thereof. The filler can be or include wet carbon black in the form of pellets, fluffy powder, granules, and / or agglomerates. The wet carbon black can be formed into pellets, granules, or agglomerates, for example, in a pelletizer, fluidized bed, or other device to make a wet filler.
[0080] The fillers used in the tire tread of the present invention may be chemically treated (e.g., chemically treated carbon black, chemically treated silica, silicon treated carbon black) and / or chemically modified. The filler may be or may include carbon black having organic group(s) attached thereto. The filler may have one or more coatings present on the filler (e.g., silicon coated material, silica coated material, carbon coated material). The filler may be oxidized and / or have other surface treatments. The filler may include at least one material selected from carbonaceous materials, carbon black, silica, nanocellulose, lignin, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, recycled carbon, reclaimed carbon, rCB, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, or their corresponding coated or chemically treated materials. There is no limitation as to the type of silica, carbon black, or other fillers that may be used. Further details regarding the filler are given in other sections herein. The filler can be or include a blend of carbon black and silica in any weight ratio, for example, in the weight ratio range of 1:99 to 99:1 or 25:75 to 75:25 or 45:55 to 55:45.
[0081] The wet carbon black can be one or more of the following: - undried carbon black pellets; and / or - dried carbon black pellets that are wetted with water, for example in a pelletizer; and / or - dried carbon black pellets that are ground in a pelletizer and then rewetted with water; and / or - dried carbon black pellets combined with water; and / or - A fluffy powder, granules or agglomerates combined with water.
[0082] In a typical carbon black production, carbon black is first prepared as a dry, finely particulate (fluffy) material. The fluffy carbon black can be densified by a conventional pelletizing process, for example, by combining the carbon black with a liquid, for example, adding water and feeding the mixture to a pin pelletizer. Pin pelletizers are well known in the art, including the pin pelletizer described in U.S. Pat. No. 3,528,785. The resulting wet pellets are then heated under controlled temperatures and parameters to remove the liquid from the pellets prior to further handling and transportation. In an alternative process, carbon black pellets can be produced by a process that omits the drying step. In such a process, the pelletized carbon black contains at least 20% by weight process water based on the total weight of the wet carbon black. These "undried carbon black" pellets can be used directly in the claimed process after pelletizing. Alternatively, dried carbon black pellets (e.g., commercially available carbon black pellets) can be rewetted in a pelletizer. The pellets may be granulated, crushed, classified, and / or crushed, for example, in a jet mill. The resulting carbon black is in fluffy form and may be repelletized in a pelletizer, or otherwise compressed or agglomerated in the presence of water to wet the carbon black. Alternatively, the fluffy carbon black may be compressed into other forms, such as brick-like forms, by equipment known in the art. As another option, the fluffy carbon black may be wetted by using a fluidized bed, sprayer, mixer, or rotating drum and the like. When the liquid is water, the undried or rewetted carbon black may achieve a moisture content of 20% to 80%, 30% to 70% by weight, or other ranges, such as 55% to 60% by weight, based on the total weight of the wet carbon black.
[0083] The carbon black used in the tire tread of the present invention may be any of the reinforcing and semi-reinforcing carbon black grades. Examples of reinforcing grades of ASTM grades are N110, N121, N134, N220, N231, N234, N299, N326, N330, N339, N347, N351, N358, and N375 carbon black. Examples of semi-reinforcing grades of ASTM grades are N539, N550, N650, N660, N683, N762, N765, N774, N787, N990 carbon black and / or N990 grade thermal black.
[0084] Carbon black, for example, is 20m 2 / g~250m 2 / g or more, e.g., at least 60m 2 / g, e.g., 60m 2 / g~150m 2 / g, or 70m 2 / g~250m 2 / g, or 80m 2 / g~200m 2 / g, or 90m 2 / g~200m 2 / g, or 100m 2 / g~180m 2 / g, 110m 2 / g~150m 2 / g, 120m 2 / g~150m 2 / g, etc., 140m 2 / g~180m 2 / g, 150m 2 / g~180m 2 / g, 140m 2 / g~170m 2 / g, 150m 2 / g~170m 2 / g, 140m 2 / g~160m 2 / g, or 150m 2 / g~160m 2The sintered body may have a statistical thickness specific surface area (STSA) in the range of 0.1 to 0.5 mm / g. STSA (statistical thickness specific surface area) is determined according to ASTM test procedure D-6556 (measured by nitrogen adsorption).
[0085] Carbon black is about 30 mL / 100 g to about 150 mL / 100 g, for example, about 30 mL / 100 g to about 125 mL / 100 g, about 30 mL / 100 g to about 115 mL / 100 g, about 50 mL / 100 g to about 150 mL / 100 g, about 50 mL / 100 g to about 125 mL / 100 g, about 50 mL / 100 g to about 115 mL / 100 g, about 70 mL / 100 g to about 150 The carbon black may have a compressed oil absorption number (COAN) in the range of 60 mL / 100g, about 70 mL / 100g to about 125 mL / 100g, about 70 mL / 100g to about 115 mL / 100g, about 80 mL / 100g to about 150 mL / 100g, about 80 mL / 100g to about 125 mL / 100g, about 80 mL / 100g to about 115 mL / 100g, or about 80 mL / 100g to about 100 mL / 100g. The compressed oil absorption number (COAN) is determined by ASTM D3493. Optionally, the carbon black has a COAN of 70 mL / 100g to 115 mL / 100g, and a COAN of 60 mL / 100g to about 150 mL / 100g. 2 / g~1555m 2 / g range.
[0086] As described, the carbon black may be rubber black, particularly reinforcing grades of carbon black or semi-reinforcing grades of carbon black. Carbon blacks sold under the trademarks Regal®, Black Pearls®, Spheron®, Sterling®, Propel®, Endure®, and Vulcan® available from Cabot Corporation, Raven®, Statex®, Furnex®, and Neotex®, and CD and HV series available from Birla Carbon (formerly Columbian Chemicals), and Corax®, Durax®, Ecorax®, and Purex®, and CK series available from Orion Engineered Carbons (formerly Evonik and Degussa Industries), and other fillers suitable for use in rubber or tire applications may also be utilized for use according to various implementations. Suitable chemically functionalized carbon blacks include those disclosed in WO 96 / 18688 and US 2013 / 0165560, the disclosures of which are incorporated herein by reference. Any mixture of these carbon blacks may be used. Carbon blacks with surface areas and structures that exceed the typical values selected for ASTM grades and blends with rubber, such as those described in US 2018 / 0282523, the disclosures of which are incorporated herein by reference, may be used in the tire tread of the present invention.
[0087] The carbon black may be an oxidized carbon black, for example, a carbon black that has been surface-treated using an oxidizing agent. The oxidizing agent may include, but is not limited to, air, oxygen gas, ozone, NO2 (including a mixture of NO2 and air), peroxides, for example, hydrogen peroxide, persulfates including sodium, potassium, or ammonium persulfate, hypohalites, for example, hypochlorous acid, haloacid, halogen acid, or sodium perhalate (for example, sodium chlorite, sodium chlorate, or sodium perchlorate), oxidizing acids, for example, nitric acid, and transition metal-containing oxidizing agents, for example, permanganates, osmium tetroxide, chromium oxide, or cerium ammonium nitrate. Mixtures of oxidizing agents may be used, particularly mixtures of gaseous oxidizing agents, for example, oxygen and ozone. In addition, carbon blacks prepared using other surface modification methods to introduce ionic or ionizable groups to the pigment surface, for example, chlorination and sulfonation, may be used. Processes that can be used to produce oxidized carbon black are known in the art, and several types of oxidized carbon black are commercially available.
[0088] The carbon black may be furnace black, gas black, thermal black, acetylene black, lamp black, plasma black, or recycled black (or rCB), or carbon products containing silicon-containing species, and / or metal-containing species, and / or the like. The carbon black may be, for the purposes of the present invention, a multiphase aggregate comprising at least one carbon phase and at least one metal-containing species or silicon-containing species phase, i.e., silicon-treated carbon black. In silicon-treated carbon black, the silicon-containing species, e.g., oxides or carbides of silicon, are distributed throughout at least a portion of the carbon black aggregate as an essential part of the carbon black. Silicon-treated carbon black is not a coated or otherwise modified carbon black aggregate, but actually represents a two-phase aggregate particle. One phase is carbon still present as graphite crystallites and / or amorphous carbon, while the second phase is silica and possibly other silicon-containing species). Thus, the silicon-containing species phase of the silicon-treated carbon black is an intrinsic part of the aggregate, being distributed throughout at least a portion of the aggregate. (商標) Silicon-treated carbon blacks are available from Cabot Corporation. The preparation and properties of these silicon-treated carbon blacks are described in U.S. Patent No. 6,028,137, the disclosure of which is incorporated herein by reference.
[0089] Silicon-treated carbon black may contain silicon-containing regions primarily at the aggregate surface of the carbon black, but still be part of the carbon black, and / or silicon-treated carbon black may contain silicon-containing regions distributed throughout the carbon black aggregate. Silicon-treated carbon black may be oxidized. Silicon-treated carbon black may contain from about 0.1% to about 50% silicon by weight, based on the weight of the silicon-treated carbon black. These amounts may be from about 0.5% to about 25% by weight, from about 1% to about 15% by weight silicon, from about 2% to about 10% by weight, from about 3% to about 8% by weight, from about 4% to about 5% by weight, or to about 6% by weight, all based on the weight of the silicon-treated carbon black.
[0090] Those skilled in the art will recognize that apart from the silicon content of silicon-treated carbon black, the surface area of the particle may also vary in the amount of silica and carbon black. For example, the surface area of the silicon-treated carbon black may contain about 5% to about 95% silica, such as about 10% to about 90%, about 15% to about 80%, about 20% to about 70%, about 25% to about 60%, about 30% to about 50%, or about 35% to about 40%, such as up to about 20% or up to about 30% silica. The amount of silica in the surface area may be determined by the difference between the surface areas of the particles as measured by iodine number (ASTM D-1510) and nitrogen adsorption (i.e., BET, ASTM D6556).
[0091] As another option, filler, for example carbon black, can be chemically treated.For example, carbon black can have at least one organic group attached.Attachment can occur via diazonium reaction, where at least one organic group has diazonium salt substituent, as detailed in, for example, U.S. Pat. No. 5,554,739; U.S. Pat. No. 5,630,868; U.S. Pat. No. 5,672,198; U.S. Pat. No. 5,707,432; U.S. Pat. No. 5,851,280; U.S. Pat. No. 5,885,335; U.S. Pat. No. 5,895,522; U.S. Pat. No. 5,900,029; U.S. Pat. No. 5,922,118, the disclosures of which are incorporated herein by reference.
[0092] In the tire tread of the present invention, more than one combination of fillers may be used in the composite of the present invention or in a compound containing said composite. The combination may include rubber reinforcing carbon black(s) and silica, e.g., precipitated silica, and the combination may include a carbon black to silica weight ratio of at least 2.7 to 1.0.
[0093] With regard to the filler, one or more types of silica, or any combination of silica(s) may be used in any embodiment of the present invention. The silica may include or be precipitated silica, fumed silica, silica gel, and / or colloidal silica. The silica may include or be untreated silica and / or chemically treated silica. Silica may be suitable for reinforcing elastomer composites, and may be present in an amount of about 20 ml. 2 / g~about 450m 2 / g; approx. 30m 2 / g~about 450m 2 / g; approx. 30m 2 / g~about 400m 2 / g; or about 60m 2 / g ~ approx. 250m 2 / g, approx. 60m 2 / g ~ approx. 250m 2 / g, approx. 80m 2 / g~about 200m 2The silica may be characterized by a Brunauer-Emmett-Teller surface area (BET) of 1000 nm / g. Highly disperse precipitated silica may be used as a filler in the present process. Highly disperse precipitated silica ("HDS") is understood to mean any silica that has a substantial ability to dissociate and disperse in an elastomeric matrix. Such a determination of dispersion may be observed in known manner by electron or optical microscopy in thin sections of the elastomer composite. Examples of commercial grades of HDS include Perkasil® GT3000GRAN silica from WR Grace & Co, Ultrasil® 7000 silica from Evonik Industries, Zeosil® 1165MP, 1115MP, Premium and 1200MP silica from Solvay SA, Hi-Sil® EZ160G silica from PPG Industries, Inc., and Zeopol® 8741 or 8745 silica from Evonik Industries. Conventional non-HDS precipitated silicas may also be used. Examples of commercial grades of conventional precipitated silica include Perkasil® KS408 silica from WR Grace & Co, Zeosil® 175GR silica from Solvay SA, Ultrasil® VN3 silica from Evonik Industries, and Hi-Sil® 243 silica from PPG Industries, Inc. Precipitated silicas having a surface with a silane coupling agent attached thereto may also be used. Examples of commercial grades of chemically treated precipitated silica include Agilon® 400, 454, or 458 silica from PPG Industries, Inc., and Coupsil silicas, such as Coupsil® 6109 silica, from Evonik Industries.
[0094] The liquid amounts in the filler described above can be equally applied to silica, but as a more specific example, when silica is used as a wet filler as part or whole of the wet filler, the silica may have a liquid present in an amount of about 25% to about 75% by weight, for example, about 30% to about 75% by weight, about 40% to about 75%, about 45% to about 75%, about 50% to about 75%, about 30% to about 70%, about 40% to about 70%, about 45% to about 70%, about 50% to about 70%, about 30% to about 65%, about 40% to about 65%, about 45% to about 65%, about 50% to about 65%, about 30% to about 60%, about 40% to about 60%, about 45% to about 60%, or about 50% to about 60% by weight, based on the weight of the total wet filler or based on the weight of only the wet silica present.
[0095] Typically, the silica (e.g., silica particles) has a silica content of at least 20% by weight, at least 25% by weight, at least 30% by weight, at least 35% by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or nearly 100% by weight or 100% by weight, or about 20% by weight to about 100% by weight, all based on the total weight of the particle. Any of the silica(s) may be chemically functionalized, for example to have attached or adsorbed chemical groups, for example attached or adsorbed organic groups. Any combination of silica(s) may be used. The silica may be partially or entirely hydrophobic silica, or silica with a hydrophobic surface, which may be silica that is hydrophobic by treatment (e.g., chemical treatment) to render the surface of the silica hydrophobic. The hydrophobic surface may be obtained by chemically modifying the silica particles with hydrophobizing silanes that do not have ionic groups, such as bis-triethoxysilylpropyl tetrasulfide. Hydrophobic surface-treated silica particles suitable for use herein may be obtained from commercial sources, such as Agilon® 454 silica and Agilon® 400 silica from PPG Industries. Silicas with low surface silanol density, such as those obtained through dehydroxylation at temperatures above 150° C. (423.15 K), for example, via a calcination process, may be used herein. Intermediate form silica (undried silica) obtained from the precipitation process in cake or paste form without drying may be added directly to the mixer as a wet filler, thus eliminating the complex drying step and other downstream processing steps used in the conventional manufacture of precipitated silica.
[0096] In any embodiment and at any step, the coupling agent may be introduced at any of the steps (or at multiple steps or points) so long as the coupling agent has an opportunity to become dispersed in the composite. The coupling agent may be or may include one or more silane coupling agents, one or more zirconate coupling agents, one or more titanate coupling agents, one or more nitro coupling agents, or any combination thereof. Coupling agents include bis(3-triethoxysilylpropyl)tetrasulfane (e.g., Si69 from Evonik Industries, Struktol SCA98 from Struktol Company), bis(3-triethoxysilylpropyl)disulfane (e.g., Si75 and Si266 from Evonik Industries, Struktol SCA985 from Struktol Company), 3-thiocyanatopropyl-triethoxysilane (e.g., Si264 from Evonik Industries), gamma-mercaptopropyl-trimethoxysilane (e.g., VP Si163 from Evonik Industries, Struktol SCA989 from Struktol Company), gamma-mercaptopropyl-triethoxysilane (e.g., VP Si163 from Evonik Industries, Struktol SCA989 from Struktol Company), β ... Si263), zirconium dineoalkanolatodi(3-mercapto)propionato-O, N,N'-bis(2-methyl-2-nitropropyl)-1,6-diaminohexane, S-(3-(triethoxysilyl)propyl)octanethioate (e.g., NXT coupling agents from Momentive, Friendly, WV), and / or coupling agents having one or more of the chemically similar or same chemical groups. Further specific examples of coupling agents by trade name include, but are not limited to, NXT Z and NXT Z-50 from Momentive, VP Si363 from Evonik Industries. The coupling agents described herein can be used to impart hydrophobic surface modification of silica (pre-coupled or pre-treated silica).It should be appreciated that any combination of elastomers, additives, and further composites may be added to the elastomer composite, for example, in a compounder.
[0097] The amount of silica (in parts per hundred rubber, or phr) present in the formed elastomeric composite may range from about 0 phr to about 200 phr, from about 1 phr to about 200 phr, or from 1 phr to 10 phr, or from 1 phr to 20 phr, or from 1 phr to 25 phr, or from 5 to 190 phr, or from 10 to 180 phr, or from about 15 phr to about 180 phr, from about 55 phr to about 150 phr, or from about It can be from 10 phr to about 100 phr, from about 20 phr to about 150 phr, from about 30 phr to about 100 phr, from about 25 phr to about 100 phr, from about 25 phr to about 80 phr, from about 35 phr to about 115 phr, from about 35 phr to about 100 phr, from about 40 phr to about 110 phr, from about 40 phr to about 100 phr, from about 40 phr to about 90 phr, from about 40 phr to about 80 phr, and the like.
[0098] Other fillers are disclosed in U.S. Patent Application Publication No. 2018 / 0282523 and European Patent No. 2423253(B1), the disclosures of which are incorporated herein by reference.
[0099] The amount of filler (e.g., wet filler alone or wet filler with other fillers) loaded into the wet filler composite and tread rubber compound is from 30 phr to 150 phr, for example, about 5 phr to 100 phr, 10 phr to 100 phr, 20 phr to 100 phr, 30 phr to 100 phr, 40 phr to 100 phr, 50 phr to 100 phr, or 5 phr to 70 phr, 10 phr to 70 phr, 20 phr to 70 phr, 30 phr to 70 phr, 35 phr to 70 phr, or 50 phr to 70 phr, 50 phr to 70 phr, or ... phr may range from 70 phr, 40 phr to 70 phr, 5 phr to 65 phr, 10 phr to 65 phr, 20 phr to 65 phr, 30 phr to 65 phr, 35 phr to 65 phr, 40 phr to 65 phr, 5 phr to 60 phr, 10 phr to 60 phr, 20 phr to 60 phr, 30 phr to 60 phr, 35 phr to 60 phr, 40 phr to 60 phr, 5 phr to 50 phr, or other amounts within or outside one or more of these ranges. Other ranges include about 15 phr to about 180 phr, about 20 phr to about 150 phr, about 25 phr to about 80 phr, about 30 phr to about 150 phr, about 35 phr to about 115 phr, about 35 phr to about 100 phr, about 40 phr to about 100 phr, about 40 phr to about 90 phr, about 40 phr to about 80 phr, about 29 phr to about 175 phr, about 40 phr to about 110 phr, about 50 phr to about 175 phr, about 60 phr to about 175 phr, and equivalent ranges. The filler, whether alone or with one or more other fillers, may be any filler disclosed herein, such as carbon black, silica, or silicon-treated carbon black.
[0100] For example, carbon black may be dispersed in the elastomer at a charge ranging from 30 phr to 70 phr, or from 40 phr to 65 phr, or from 40 phr to 60 phr. More specifically, the elastomer may be natural rubber alone or one or more other elastomers, the filler may be carbon black alone or one or more other fillers (e.g., silica or silicon-treated carbon black), and the carbon black may be dispersed in the natural rubber at a charge ranging from 30 phr to 70 phr, or from 40 phr to 65 phr, or from 40 phr to 60 phr.
[0101] The tires and treads of the invention may be made with compounds prepared by curing certain wet-mixed composites. Such composites may be made by introducing the solid elastomer and the wet filler into a mixer in one or multiple steps or additions. The solid elastomer may be masticated to a temperature of about 90° C. (363.15 K) or 100° C. (373.15 K) or higher before introducing the wet filler into the mixer. Alternatively, the solid elastomer may be masticated with at least a portion of the wet filler to a temperature of about 90° C. (363.15 K) or 100° C. (373.15 K) or higher before the start of any actual dispersion of the filler.
[0102] With respect to mixing, mixing may be performed in one or more mixing steps. Mixing begins when at least the solid elastomer and wet filler are dosed into the mixer and energy is applied to the mixing system that drives one or more rotors of the mixer. The one or more mixing steps may occur after the dosing step is completed or may overlap with the dosing step for any length of time. For purposes of this invention, the dosing step is completed before the mixing step is completed.
[0103] During mixing, at least some liquid present in the mixture and / or the wet filler introduced is at least partially removed by evaporation. Optionally, a majority (in weight percent) of any liquid from the mixture is removed by evaporation. For example, at least 50% by weight of the liquid is removed based on the total weight of liquid removed during mixing. The total weight of liquid removed can be determined from the difference between the liquid content of the wet filler and any liquid remaining in the composite when it is discharged from the mixer and any liquid present in or discharged from the mixer when the composite is discharged from the mixer. For example, when the composite is discharged, additional liquid (e.g., non-evaporated liquid) may be discharged either with or within the composite or through an outlet provided in the mixer. The liquid removal by evaporation can represent at least 70% by weight, at least 80% by weight, or 51% to 100% by weight, or 51% to 95% by weight of the total liquid contained in the wet filler introduced into the mixer. Optionally, one or more mixing steps or stages can further remove a portion of the liquid from the mixture by squeezing, compressing, and / or squeezing, or any combination thereof.
[0104] With regard to the mixers that may be used to prepare the composite, any suitable mixer capable of combining (e.g., mixing or blending together) the filler with the solid elastomer may be utilized. The mixer(s) may be a batch mixer or a semi-continuous or continuous mixer. A combination of mixers and processes may be utilized, and the mixers may be used in tandem sequence and / or integrated with other processing equipment. The mixer may be an internal or closed mixer or an open mixer, or an extruder or a continuous mixer or a kneading mixer, or a combination thereof. The mixer may be capable of incorporating the filler into the solid elastomer and / or dispersing the filler into the elastomer and / or distributing the filler into the elastomer. Any one or combination of commercially available mixers for making rubber compounds may be used in the present method.
[0105] The top of a typical batch mixing chamber may be raised or lowered by an air or hydraulic piston commonly referred to as a "floating weight" or "ram." The ram is raised to deliver the materials (e.g., at least the solid elastomer and wet filler) and lowered to apply pressure to the mixture to keep it within the mixing chamber. Typically, the fill factor of the batch and the ram pressure are selected to allow the ram to reach its lowest position to minimize the gap between the ram and the rotor, thereby allowing good filler distribution. The vertical distance of the ram beyond its minimum position is known as the "ram deflection."
[0106] The mixer may have one or more rotors (at least one rotor). For example, each rotor may rotate in its own cylindrical chamber, which may be connected to the chamber(s) of the other rotor(s). The shaft is controlled by the mixing system to which energy (electrical energy) is applied. The rotor may be considered as a device that provides energy to the mixture and / or a component that forms the mixture. The rotor may be designed with internal circuits or channels for steam or water or other fluids for cooling and / or heating. The at least one rotor or one or more rotors may be a screw type rotor, a cross-counter type rotor, a tangential rotor, a kneading rotor(s), a rotor used in an extruder, a roll mill that provides a significant total specific energy, or a creeper mill.
[0107] One or more mixing steps may be a single mixing step, for example a one-stage or single-stage mixing step or process, where the mixing is carried out under one or more of the following conditions: at least one of the mixer temperatures is controlled by a temperature-controlled means having one or more rotors operating at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, or at least one temperature-controlled means set at a temperature Tz of 65° C. (338.15 K) or higher, or the mixing is carried out in the substantial absence of one or more rubber chemicals before the mixer reaches the indicated temperature. In certain cases, in a single stage or single mixing step, the composite may be discharged with a liquid content of 10% by weight or less. In other embodiments, two or more mixing steps or mixing stages may be carried out, as long as one of the mixing steps is carried out under one or more of the conditions described above.
[0108] In multi-stage mixing, optionally, a second or any number of subsequent mixing stages can improve compound (or composite) properties compared to composites mixed by only a first stage of material mixing. In other words, composites formed from single-stage mixing can be comparable to composites formed from an additional stage mixing process, e.g., subjected to a second stage. When such multi-stage mixing is utilized, one or more of the composite properties (e.g., loss tangent and / or modulus ratio) can be improved. The improvement can be 5%, 10%, or 15% or more improvement in one or more properties compared to composites from only single-stage mixing. This improvement can be obtained regardless of the type of filler used and regardless of the type of elastomeric filler.
[0109] In certain embodiments, the method includes performing mixing at a controlled mixer temperature, for example, through the use of at least one temperature control means. Controlling the mixer temperature refers to controlling the temperature of at least one surface of the mixer. Optionally, the mixer temperature can be controlled during both the dosing and at least one of the mixing steps. The temperature control means can be a temperature control device on and / or within the mixer, or in other cases associated with (e.g., connected to) the mixer that heats or cools at least one surface and / or one or more parts of the mixer.
[0110] The temperature control means can be, but is not limited to, the flow or circulation of a heat transfer fluid through channels in one or more parts of the mixer. For example, the heat transfer fluid can be water or a heat transfer oil. For example, the heat transfer fluid can flow through the rotor, the mixing chamber walls, the ram, and the drop door.
[0111] The temperature of the at least one temperature control means may be set and maintained, by way of example, by one or more temperature control units ("TCUs"). This set temperature, or TCU temperature, is also referred to herein as "T z For temperature control means incorporating a heat transfer fluid, T z is a measure of the temperature of the fluid itself. The heating or cooling applied by the temperature control means is z depending on the mixer, heat is conducted to at least one surface of the mixer or to one or more parts of the mixer; heat is conducted to or from the at least one surface and then to or from the material in the mixer to affect a temperature of the mixture or a portion thereof, e.g., a local temperature of the mixture.
[0112] The mixer may have thermocouples located in different parts of the mixer to give a more accurate measurement of the temperature of the mixer section(s) or mixture.
[0113] The optimum Tz value can be selected based on the type of filler. For example, for fillers including carbon black and silicon-treated carbon black (e.g., at least 50%, at least 75%, at least 90%, or all or substantially all of the filler is carbon black), Tz can have the value described herein, for example, 65°C (338.15K) or more, or 65°C (338.15K) to 100°C (373.15K). When the filler is silica, the Tz value may be in the range of 40°C (313.15K) to 100°C (373.15K), for example, 40°C (313.15K) to 90°C (363.15K), 40°C (313.15K) to 80°C, 40°C (313.15K) to 75°C (348.15K), 50°C (323.15K) to 100°C (373.15K), 50°C (323.15K) to 90°C (363.15K), 50°C (323.15K) to 80°C, or 50°C (323.15K) to 75°C (348.15K).
[0114] The energy applied to the mixture during the mixing step can be controlled through mixer settings and process controls. For example, in a batch mixer, the total specific energy takes into account the energy applied to the rotor(s) between the input of solid elastomer and / or wet filler and the discharge per kg of composite on a dry weight basis. In a continuous mixer, the total specific energy is the input per kg of output on a dry weight basis at steady state conditions. In a process with multi-stage mixing, the total specific energy is the sum of the specific energies from each mixing process. The determination of the total specific energy preferably does not include the amount of energy used to mold or form the discharged composite (e.g., excluding the energy of roll milling the composite). The resulting "total specific energy" is the energy E applied to the mixing system driving one or more rotors per mass of composite on a dry weight basis, as defined herein. R (e.g., electrical energy). This total specific energy is also E 合計As described herein, the present process imparts total specific energy under selected operating conditions that balance longer mixing times with evaporation or removal of water in a reasonable amount of time.
[0115] Optionally, the process includes performing mixing in at least one of the mixing steps such that the resulting total specific energy is at least 1,400 kJ or at least 1,500 kJ per kg of composite, e.g., at least 1,600 kJ / kg, at least 1,700 kJ / kg, at least 1,800 kJ / kg, at least 1,900 kJ / kg, at least 2,000 kJ / kg, at least 2,500 kJ / kg, or at least 3,000 kJ / kg. Optionally, the total specific energy is from about 1,400 kJ / kg of composite or from about 1,500 kJ / kg of composite (or per kg of mixture present in the mixer) to about 10,000 kJ / kg of composite (or per kg of mixture present in the mixer), for example, from 2,000 kJ / kg to about 5,000 kJ, or from 1,500 kJ / kg to 8,000 kJ / kg, from 1,500 kJ / kg to 7,000 kJ / kg, from 1,500 kJ / kg to 6,000 kJ / kg, The range may be from 1,500 kJ / kg to 5,000 kJ / kg, from 1,500 kJ / kg to 3,000 kJ / kg, from 1,600 kJ / kg to 8,000 kJ / kg, from 1,600 kJ / kg to 7,000 kJ / kg, from 1,600 kJ / kg to 6,000 kJ / kg, from 1,600 kJ / kg to 5,000 kJ / kg, from 1,600 kJ / kg to 4,000 kJ / kg, from 1,600 kJ / kg to 3,000 kJ / kg, or other values within any of these ranges.
[0116] Optionally, the process includes performing mixing such that in at least one of the mixing steps, one or more rotors operate at a tip speed of at least 0.5 m / s for at least 50% of the mixing time or at a tip speed of at least 0.6 m / s for at least 50% of the mixing time. The energy input to the mixing system is at least in part a function of the speed of at least one rotor and the type of rotor. The tip speed, taking into account the rotor diameter and rotor speed, can be calculated by the following formula: Tip speed (m / s) = π × (rotor diameter, m) × (rotational speed, rpm) / 60.
[0117] Since the tip speed may vary over the course of mixing, optionally a tip speed of at least 0.5 m / s or at least 0.6 m / s is achieved for at least 50% of the mixing time, e.g., at least 60%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, or for substantially all of the mixing time. The tip speed may be at least 0.6 m / s, at least 0.7 m / s, at least 0.8 m / s, at least 0.9 m / s, at least 1.0 m / s, at least 1.1 m / s, at least 1.2 m / s, at least 1.5 m / s, or at least 2 m / s for at least 50% of the mixing time, or during other portions of the mixing as listed above. The tip speed may be selected to minimize the mixing time, or to be between 0.6 m / s and 10 m / s, between 0.6 m / s and 8 m / s, between 0.6 and 6 m / s, between 0.6 m / s and 4 m / s, between 0.6 m / s and 3 m / s, between 0.6 m / s and 2 m / s, between 0.7 m / s and 4 m / s, between 0.7 m / s and 3 m / s, between 0.7 m / s and 2 m / s, between 0.7 m / s and 10 m / s (e.g., for at least 50% of the mixing time or other mixing times described herein). In the alternative or in addition, the tip speed may be selected to be maximized throughout.
[0118] The wet mixed composite may be discharged from the mixer with the filler dispersed in the elastomer at a charge of at least 20 phr with no more than 10% filler yield loss and no more than 10% liquid content by weight of the total composite. Discharge ("damping" in batch mixing) may be based on time or temperature or specific energy or power parameters selected to minimize rubber degradation. In one embodiment, the mixing time may be determined from the period when dosing is complete to the time of discharge. In a batch internal mixer, the mixing time may be determined from the ram down time, the time when the ram is operating at its lowest position and is completely closed. In another embodiment, the lowest position of the ram (i.e., its fully seated position) may allow for a certain amount of ram deflection. The mixing time does not include the period when additional ingredients are dosed, e.g., when one or more additional portions of elastomer and / or filler are dosed. Optionally, in a continuous mixer, the nominal mixing time (or residence time) may be calculated from the mixer chamber volume and the volumetric production rate.
[0119] Optionally, the discharge is based on a prescribed mixing time. The mixing time between the start of mixing and the discharge can be about 1 minute or more, for example, about 1 minute to 40 minutes, about 1 minute to 30 minutes, about 1 minute to 20 minutes, or 1 minute to 15 minutes, or 5 minutes to 30 minutes, or 5 minutes to 20 minutes, or 5 minutes to 15 minutes, or 1 minute to 12 minutes, or 1 minute to 10 minutes, or 3 minutes to 30 minutes, or other times. Alternatively, for batch internal mixers, the ram down time can be used as a parameter to monitor the time related to the batch mixing time. For example, the ram down time can be in the range of 3 minutes to 30 minutes, 3 minutes to 20 minutes, 3 minutes to 10 minutes, 5 minutes to 30 minutes, 5 minutes to 20 minutes, 5 minutes to 10 minutes.
[0120] Optionally, the discharge is based on damping or on the discharge temperature. For example, the mixer may have a damping temperature in the range of 120°C (393.15K) to 180°C (453.15K), 120°C (393.15K) to 190°C (463.15K), 130°C (403.15K) to 180°C (453.15K), e.g., 140°C (413.15K) to 180°C (453.15K), 150°C (423.15K) to 180°C (453.15K), 130°C (403.15K) to 170°C (443.15K), 140°C (413.15K) to 170°C (443.15K), 150°C (423.15K) to 170°C (443.15K), or other temperatures within or outside these ranges.
[0121] The extruded composite may have a liquid content of 10% by weight or less, based on the total weight of the composite, as outlined in the following formula: Liquid content of the complex (%) = 100 * [mass of liquid] / [mass of liquid + mass of dry complex]
[0122] The discharged wet mixed composite may have a liquid content of 10% or less by weight based on the total weight of the composite, for example, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 2% or less, or 1% or less by weight based on the total weight of the composite. This amount may range from about 0.1% to 10% by weight, or from about 0.5% to 9% by weight, or from about 0.5% to about 7% by weight based on the total weight of the composite discharged from the mixer at the end of the process. The liquid content (or "moisture content") may be the measured weight percent of liquid present in the composite based on the total weight of the composite. There may optionally be additional liquid present in the mixer that is not retained in the composite that is discharged. This excess liquid is not part of any calculated liquid content of the composite.
[0123] Filler yield loss is determined based on subtracting the measured phr of filler in the extruded composite from the theoretical maximum phr of filler in the elastomer (assuming all filler entering the mixer is incorporated into the composite). Filler that is flaked off at the surface of the composite due to insufficient incorporation of the filler into the elastomer is included in the filler yield loss. This measurement can be obtained from thermogravimetric analysis (TGA). Thus, the filler yield loss (%) is calculated as follows: [((Theoretical phr of filler)-(Measured phr of filler)) / ((Theoretical phr of filler))] x 100
[0124] Optionally, the fill factor (on a dry weight basis) of the wet filler and solid elastomer including natural rubber may be 70% or less, or 68% or less, for example, in the range of 60% to 70%, 60% to 68%, or 65% to 68%. Such conditions may be used for solid elastomers including at least 50%, at least 75%, at least 90%, or at least 95% natural rubber, such as blends of natural rubber and at least one additional elastomer, such as polybutadiene and / or styrene-butadiene rubber, or other elastomers disclosed herein.
[0125] Optionally, the liquid release rate, including but not necessarily limited to the evaporation rate of liquid from the composite during mixing, may be measured as the time-averaged release rate of liquid per kg of composite, which may be 0.01-0.14 kg / (min·kg) or 0.01-0.07 kg / (min·kg) or other rates below or above this range. This release rate may be the total release rate of liquid removal by any means during mixing, or may be the release rate due to evaporation alone. In the case of aqueous liquids, the evaporation rate may be the vapor release or vapor generation rate. Release rates below 0.01 kg / (min·kg) may generally indicate longer times to remove liquid, for example, at Tz below 65° C. (338.15 K) and / or specific energy levels below 1,500 kJ / kg, and / or tip speeds below 0.5 m / s or below 0.6 m / s. Release rates above 0.15 kg / (min·kg) may indicate shorter mixing times. If the time-average release rate is not optimized, poor dispersion and rubber properties may result.
[0126] Optionally, the maximum pressure can be controlled. When the mixer is a batch mixer with a ram, the pressure in the mixer chamber can be influenced by controlling the pressure applied to the ram cylinder.
[0127] Optionally, a multi-stage mixing process may be used to create the wet mixed composite, having at least two mixing steps or stages. These two (or more) mixing steps may be multi-step or multi-stage mixing, having a first mixing step or stage and at least a second mixing step or stage. One or more of the multi-stage mixing processes may be batch, continuous, semi-continuous, and combinations thereof.
[0128] With respect to the multi-step process, the method of preparing the composite includes the step of charging or introducing at least a) one or more solid elastomers and b) one or more fillers into a first mixer, where at least one filler or a portion of at least one filler is a wet filler as described herein (e.g., a wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler) by any of the methods described herein. The solid elastomer is combined with the wet filler to form a mixture or composite during this mixing step(s), which may be considered a first mixing step or stage. The method further includes mixing the mixture in this first mixing step to an extent that at least a portion of the liquid is removed by evaporation or an evaporation process carried out during mixing. This first mixing step (in one or more mixing steps) or stage is carried out using one or more of the processes described above for forming a composite, with the understanding that it is not required that the mixture discharged from the mixer after the first mixing step (e.g., the discharged mixture) has a liquid content of 10% by weight or less after the completion of the first mixing. That is, with a multi-stage process(es), the mixture resulting from the first mixer (or first mixing step) upon completion of the first mixing may have a liquid content of more than 10% by weight, but will not have a reduced liquid content (in weight %) compared to the liquid content of the combined solid elastomer and wet filler at the start of the first mixing step, e.g., a liquid content reduced to an amount less than the liquid content at the beginning of any subsequent mixing step, e.g., a liquid content reduced by at least 50% by weight.
[0129] The method then includes mixing or further mixing the mixture in at least a second mixing step or stage using the same mixer (i.e., the first mixer) and / or utilizing a second mixer(s) different from the first mixer.
[0130] After the first mixing, the further mixing step(s) performed for multi-stage mixing can utilize any one or more of the mixing procedures or parameters or steps utilized in the first mixing step described herein. Thus, in performing the further mixing steps or steps, the same or different mixer design and / or the same or different operating parameters as the first mixer can be used in the further mixing steps. The mixers and options thereof described above for the first mixing step and / or the operating parameters described above for the mixing steps can optionally be used in the further or second mixing steps (e.g., mixing steps described herein including a tip speed of at least 0.5 m / s for at least 50% of the time or at least 0.6 m / s for at least 50% of the time, and / or a Tz of 50° C. (323.15 K) or higher, 60° C. (333.15 K) or higher, or 65° C. (338.15 K) or higher). Thus, the method of preparing a composite with multi-stage mixing can utilize one or more of the following parameters in at least one of the mixing steps, at least two of the mixing steps, or all of the mixing steps: At least one temperature control means is set to a temperature Tz of 65° C. (338.15 K) or greater during said mixing; and / or During said mixing, one or more rotors are operated at a tip speed of at least 0.5 m / s for at least 50% of the mixing time to produce a composite with a resulting total specific energy of at least 1500 kJ / kg; and / or Optionally adding at least one additive selected from antidegradants and coupling agents during said dosing (a) or during said mixing (b), and optionally adding one or more rubber chemicals after the mixer has reached a temperature of 120° C. (393.15 K) or greater; and / or said dosing (a) and said mixing (b) are carried out in the substantial absence of one or more rubber chemicals before the mixer reaches the indicated temperature; and / or The mixer has a fill factor, based on the dry weight of at least the solid elastomer and the wet filler, of no more than 72%.
[0131] During mixing in the second mixer, the ram pressure may be relieved, for example, under one or more of the following conditions: (i) The ram may be installed, but the ram may be subjected to pressure (e.g., 5 psi (3.448275 x 10 -2 Essentially no pressure (up to 100 Pa) is applied. (ii) The ram is raised to at least 75% of its maximum level. Some mixers allow the ram to be positioned at a certain height. A ram in a fully seated position is at 0% of its maximum level as opposed to being raised to its maximum level or fully open position, which is the typical position of the ram when material is charged into the mixer. A ram that is positioned at a height of at least 75% of its maximum level is raised, for example, at least 80%, at least 85%, at least 90%, at least 95%, or fully, to its maximum level (100%) to ensure minimal contact between the ram and the elastomer charged into the mixer. (iii) When no pressure is applied to the mixing chamber, certain rams may operate as floating weights, e.g., in a floating configuration. The ram may come into contact with the elastomer, but the applied pressure is minimal. (iv) The ram is positioned so that it does not substantially contact the mixture. When the content has a low fill factor, e.g., 25%, it may not be necessary to position the ram height to at least 75% of its maximum level. The ram can be positioned at a height such that it does not substantially contact the mixture, e.g., 10% or less (by area) of the face of the ram contacts the mixture, e.g., 5% or less of the face of the ram, or 0% of the face of the ram does not contact the mixture. (v) Select a mixer without a ram. (vi) The fill factor of the mixture is in the range of 25% to 70%, e.g., 25% to 60%, 25% to 55%, 25% to 50%, 25% to 45%, 25% to 40%, 30% to 70%, 30% to 60%, 30% to 55%, 30% to 50%, 30% to 45%, 30% to 40%, 35% to 70%, 35% to 60%, 35% to 55%, 35% to 50%, 35% to 45%, or 35% to 40%, on a dry weight basis. By controlling the fill factor, it may be unnecessary to manipulate the ram operation or position.
[0132] Optionally, after the composite is discharged from the second mixer, it may be subjected to further mastication, for example by mixing in either the first or second mixer, or in a third mixer.
[0133] Tires, treads and compounds The treads and tires may be compounded, built, molded, shaped and cured by a variety of methods that will be readily apparent to those skilled in the art.
[0134] The tire tread of the present invention may include one or more superimposed elastomeric layers, for example one or more rubber compounds extruded into an inner or lower layer between the tire carcass, or belt, and the road-contacting outer layer or cap. One or more additional layers or zonal layers superimposed within the cap or inner layer may be used. Alternatively, the tire tread of the present invention may include a multi-zonal elastomeric layer. For example, an axial zone across the tire tread may be made with one rubber compound at the equatorial plane and one or more different rubber compound(s) at the lateral outer planes. A similar zonal configuration may be used in one or more tread inner layers. The volume of the voids (grooves or sipes) may vary across the multi-zonal configuration with or without the selection of different rubber compounds in such zones. The thickness of the elastomeric layer may vary. The composites of the present invention may be used in rubber compounds for the outer layers of treads and for the equatorial zone of multi-zone treads to improve wear resistance and rubber performance in areas of greatest stress during tire operation without excessive heat generation.
[0135] In addition, the tires and tire treads of the present invention may contain rubber compounds made by composites in the shoulder areas of the inner tread and carcass construction, which tend to be subject to high mechanical stresses, especially in trucks and heavy vehicles. Such rubber compound zones or beads may be used in multi-zone inner layer designs, for example with excellent low heat generation rubber compounds in the lower mechanical stress parts of the inner layer of the tread, with very low loss tangents. The use of the present invention in such shoulder areas also extends the useful tire life for truck and other heavy vehicle tires, since it facilitates retreading.
[0136] The rubber compounds of the treads and tires according to the invention may contain, in addition to the composites of the invention, for example, plasticizers including processing oils and resins, pigments, antioxidants, anti-ozone waxes, crosslinking systems based either on sulfur and / or peroxides and / or bismaleimides, crosslinking activators including zinc monoxide and stearic acid, extender oils, one or more agents for coating the silica, such as alkoxysilanes, polyols or amines.
[0137] It is easily understood by those skilled in the relevant art that the rubber composition (e.g., made from the composite of the present invention) can be compounded by methods generally known in the rubber compounding field, for example, by mixing the sulfur vulcanizable constituent rubber with various commonly used rubber additives, such as crosslinking coagents, such as sulfur, activators, retarders and accelerators, processing additives, such as rubber processing oils, resins including tackifying resins, silica, and plasticizers, fillers, pigments, fatty acids, zinc oxide, waxes, antioxidants and antiozonants, peptizers and reinforcing materials, such as reinforcing particles, fibers, granules and platelets, such as carbon black and silica, and combinations thereof. As known to those skilled in the art, depending on the intended use of the sulfur vulcanizable material (rubber) and the sulfur vulcanized material (rubber), the additives mentioned above are selected and generally used in effective amounts and are incorporated into the compound at an optimized mixing process stage.
[0138] The rubber compounds may be extended using paraffinic, aromatic or naphthenic oils in amounts between 0 and 50 phr of extender oil. As an option made possible by the composites of the present invention, extender oils and resins may be used in smaller amounts, for example 5 phr or less, or 2 phr or less, to obtain better mechanical properties and wear resistance in the rubber compounds and tire treads, and to improve the processability of compounds with very low oil or resin levels.
[0139] When used in the compound, fatty acids, such as stearic acid, may be added in an amount of about 0.5 to about 3 phr. Typical amounts of zinc oxide may be about 1 to about 5 phr. Typical amounts of wax may be about 1 to about 5 phr. Microcrystalline wax may be used. Typical amounts of deflocculating agents may be about 0.1 to about 1 phr. Typical deflocculating agents may be, for example, pentachlorothiophenol and dibenzamidodiphenyl disulfide.
[0140] Vulcanization is carried out in the presence of a sulfur vulcanizing agent. Examples of suitable sulfur vulcanizing agents include elemental sulfur (free sulfur) or sulfur donating vulcanizing agents, such as amine disulfides, polymeric polysulfides, or sulfur olefin adducts. Preferably, the sulfur vulcanizing agent is elemental sulfur. As known to those skilled in the art, sulfur vulcanizing agents are used in amounts ranging from about 0.5 to about 4 phr, or even up to about 8 phr, about 1.5 to about 2.5 phr, and sometimes preferably from about 2 to about 2.5 phr, in some circumstances.
[0141] Accelerators are used to control the time and / or temperature required for vulcanization and to improve the properties of the vulcanizate. In one embodiment, a single accelerator system may be used, i.e., a primary accelerator. The primary accelerator(s) may be used in a total amount ranging from about 0.5 to about 4 phr, preferably from about 0.8 to about 2.5 phr. In another embodiment, a combination of primary and secondary accelerators may be used, with the second accelerator used in a smaller amount (about 0.05 to about 3 phr) to activate and improve the properties of the vulcanizate. These accelerator combinations are expected to produce a synergistic effect on the final properties, which may be somewhat better than that produced by the use of either accelerator alone. In addition, delayed action accelerators may be used that are not affected by normal processing temperatures but produce a sufficient effect at normal vulcanization temperatures. Vulcanization retarders may also be used.
[0142] Suitable types of accelerators that can be used are amines, disulfides, guanidines, thioureas, thiazoles, thiurams, sulfenamides, dithiocarbamates and xanthates. Preferably, the primary accelerator is a sulfenamide. When a second accelerator is used, the secondary accelerator is preferably a guanidine, dithiocarbamate or thiuram compound.
[0143] In practice, the tread rubber composition may be prepared, for example, in at least one non-productive mixing step in an internal rubber mixer, and often in a sequential series of at least one, usually two, separate and individual, preliminary internal rubber mixing steps, or stages, in which the composite is first mixed with any further fillers or elastomers or other additives (the "minor portion"), followed by a finishing mixing step (the "productive" mixing step) in an internal rubber mixer, or optionally in an open mill mixer, in which the curatives (sulfur and sulfur vulcanization accelerators) are blended at lower temperatures and for a substantially shorter period of time.
[0144] Typically, after each internal rubber mixing step, the rubber mixture (composition) is removed from the rubber mixer, cooled to a temperature below 40° C. (313.15 K), for example, to a temperature in the range of about 20° C. (293.15 K) to about 40° C. (313.15 K), and then added back to the internal rubber mixer for the next successive mixing step, or stage. Such temperature selection and handling techniques for non-productive followed by productive mix stages are well known to those skilled in the art.
[0145] The mixing of the finished rubber composition may be accomplished by such a sequential mixing process. The ingredients may be mixed in at least two stages, namely, at least one "non-productive" or preliminary stage, followed by a productive mix stage. The finishing curatives are typically mixed in the productive or finishing mix stage, where mixing typically occurs at a lower temperature (maximum or highest temperature) than the mixing temperature(s) of the preceding non-productive mix step(s).
[0146] Formation of the tire tread or other component is completed by conventional means, such as, for example, extrusion or calendaring or molding of the rubber composition to provide a molded, unvulcanized rubber article or component, such as a tire tread layer, or a complete tread ready for assembly. Such forming and fabrication operations are well known to those skilled in the art.
[0147] It is understood that a tire as a manufactured article is prepared by molding and curing an assembly of its components at elevated temperatures (e.g., 140° C. (413.15 K) to 170° C. (443.15 K)) and pressures in a suitable mold.
[0148] Generally, for any of the tire treads described herein, a tire including one of the tire treads is another aspect of the invention.
[0149] The tires and tire treads may fit on vehicles such as, but not limited to, vehicles that haul heavy loads and operate at sustained speeds, such as trucks, tractors, trailers, or buses.
[0150] For example, the tire of the present invention may be a pneumatic tire having a tread with radial carcass reinforcement and an additional layer or zone of elastomeric material (i.e., rubber compound) intended to fit vehicles carrying heavy loads and operating at sustained speeds, such as trucks, tractors, trailers or buses.
[0151] Alternatively, the tires and tire treads may be fitted to vehicles, such as light trucks, passenger cars, performance cars, motorcycles, off-road vehicles, construction equipment vehicles, aircraft, and other vehicles including road-fitted vehicles having a rubber tread that is mounted on the road.
[0152] Specific examples of tires and fillers, elastomers, and / or other parameters of the present invention include the following:
[0153] The tire may be an off-road vehicle or construction equipment vehicle tire, the tread being made of 60 to 100 phr of elastomer containing at least one natural or synthetic polyisoprene, and at least 130 m 2 and at least 40 phr of filler comprising at least one carbon black having a BET of 1.0 ml / g and a COAN of 115 ml / g or less.
[0154] The tire may be an off-road or construction vehicle tire, the tread further comprising at least one styrene butadiene copolymer, or butadiene polymer, or a combination thereof.
[0155] The tire may be an off-road vehicle or construction equipment vehicle tire, the tread being made of 60 to 100 phr of elastomer containing at least one natural or synthetic polyisoprene, and at least 130 m 2 At least 40 phr of filler including at least one carbon black having a BET of 150 ml / g and a COAN of 115 ml / g or less, and 5 to 10 phr of at least one silica. For example, the tire may be an off-road vehicle or construction vehicle tire, the tread being 150 m 2 The composition further comprises at least one carbon black having a BET greater than 100 ml / g, an OAN less than 100 ml / g, and a COAN less than 90 ml / g.
[0156] The tire may be a high performance automobile or motorcycle tire, the tread comprising 100 phr of elastomer comprising at least one polymer selected from solution styrene butadiene copolymers and butadiene polymers and combinations thereof, and 150 to 220 m 2 At least one carbon black having an STSA of 150 to 200 m 2 / g BET of at least 40 phr of filler including at least one silica.
[0157] The tire may be a truck or bus tire, the tread being made of 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer and at least 115 m 2 at least 30 phr of filler comprising at least one carbon black having an STSA of 100 ml / g and a COAN of less than 110 ml / g, and 1 to 25 phr of at least one silica filler.
[0158] The tire may be a truck or bus tire, the tread being made of 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer and at least 115 m 2 45-60 phr of filler comprising at least one carbon black having an STSA of 100 ml / g and a COAN of less than 110 ml / g, and 1-25 phr of at least one silica filler.
[0159] The tire may be a truck or bus tire, the tread being made of 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer and 150 m 2 at least 30 phr of filler comprising at least one carbon black having a BET greater than 100 ml / g, an OAN less than 100 ml / g, and a COAN less than 90 ml / g, and 1 to 25 phr of at least one silica filler.
[0160] The tire may be a truck or bus tire, the shoulder component of the tread being comprised of 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer and at least 120 m 2 at least 40 phr of filler comprising at least one carbon black having a BET of 100 ml / g and a COAN of less than 110 ml / g, and 1 to 20 phr of at least one silica filler.
[0161] The tire may be a truck or bus tire, the shoulder component of the tread comprising 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer, and 150 m2 at least 40 phr of filler comprising at least one carbon black having a BET greater than 100 ml / g, an OAN less than 100 ml / g, and a COAN less than 90 ml / g, and 1 to 25 phr of at least one silica filler.
[0162] The tire has a tread underlayer of 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer, polybutadiene elastomer, or a combination thereof, and a 100m 2 and at least 40 phr of filler comprising at least one carbon black having a BET of less than 100 g / kg and an I2 value of less than 110 g / kg.
[0163] The tire may have a tire tread including at least 20 phr of a filler including at least one carbon black selected from surface modified carbon black, oxidized carbon black, multiphase aggregate carbon black (e.g., ECOBLACK™ material), and carbon black having an areal hydrogen content of at least 2000 ppm.
[0164] Optionally, the wet mix composite may be used or manufactured for use (e.g., to form an incorporated vulcanizate) in pneumatic tires as well as non-pneumatic or solid tires in various parts of the tire other than the tire tread, such as the base, undertread, innerliner, tire sidewall, tire sidewall insert, wire skim for tires, and cushion rubber for retread tires.
[0165] In some embodiments, the composites and formulations described herein can be used in a variety of tire designs, such as those described in U.S. Pat. Nos. 3,157,218; 6,247,512; 8,936,056; 9,713,943; 10,308,073; 6,540,858; 9,649,883; 8,302,643; 9,713,942; 8,720,508; 8,939,183; 9,387,728; 9,783,004; 10,245,891; 10,336,14 No. 7,028,734; No. 7,735,533; No. 8,695,662; No. 8,936,056; No. 10,399,386; No. 10,543,718; U.S. Patent Application Publication Nos. 2019 / 0351716 and 2020 / 0070577; and WO 2018 / 122496A1; WO 2014 / 102136A1; WO 2019 / 092361A1; and WO 2019 / 122618A1.
[0166] With respect to the present invention, any "option" or "optional feature" can be combined with other optional features. It should be understood that the disclosure herein refers to certain illustrated examples, which are presented by way of example and not limitation. The contents of the above detailed description discuss preferred examples, but should be construed to cover all modifications, alternatives, and equivalents of the examples as may be within the spirit and scope of the invention as defined by further disclosure.
[0167] The entire contents of all cited references in this disclosure are incorporated herein by reference to the extent they are not inconsistent with the present disclosure.
[0168] The present invention may include any combination of the various features or embodiments described above and / or in the claims, as set forth in sentences and / or paragraphs. Any combination of features disclosed herein is considered part of the present invention, and no limitation is intended with respect to features that may be combined.
[0169] Other embodiments of the invention will be apparent to those skilled in the art from consideration of the specification and practice of the invention disclosed herein. It is intended that the specification and examples be considered as exemplary only, with a true scope and spirit of the invention being indicated by the following claims and equivalents thereof. EXAMPLES
[0170] The examples describe the preparation of wet mixed composites (masterbatches), compounds prepared from the masterbatches, and corresponding vulcanized tire treads of the invention (samples E1, E3), as well as comparative materials (samples C1 and C2).
[0171] Examples 1-3 Sample E1 Preparation of wet mixed complex For the wet mix composite used to prepare the rubber compound for the tire tread of the present invention (Sample E1), the wet carbon black was obtained by jet milling N234 carbon black pellets (Vulcan® 7H carbon black obtained from Cabot Corporation) and re-pelletizing and wetting the dried milled carbon black with reverse osmosis (RO) treated water in a pin pelletizer. The moisture content of the wet carbon black ranged from 54-60%, based on the weight of the wet carbon black.
[0172] Mixing of the wet-mix composite using wet carbon black and solid natural rubber was carried out in a two-stage mixing process with a target filler loading of 51 phr. The first stage of mixing to form the composite was carried out in a Kobelco BB-72 tangential mixer fitted with a 4WN rotor with a net volume of 66.2 L according to the mixing protocol in Table 1A. The resulting mixture was transferred to a TSR-125 twin screw damping extruder (Kobelco Kobe Steel Group) fitted with fixed blades for further processing and discharged into a second mixer for the second stage of mixing. The second stage of mixing was carried out in a Kobelco BB-16 tangential mixer (14.4 L volume) fitted with a 6WI rotor according to the mixing protocol in Table 1B, where mastication and water evaporation were completed to obtain the composite using an automatic control unit that maintained the temperature of the mixture (at a constant value of 135°C (408.15K)) by varying the rpm of the mixer. The resulting mixture was transferred to a twin screw damping extruder (Kobelco Kobe Steel Group) fitted with a roller die and converted into a composite sheet.Standard grade RSS3 natural rubber (Von Bundit Co., Thailand) was used and antidegradant (2phr 6PPD) was added during the first stage of mixing. [Table 1A] [Table 1B]
[0173] Preparation of Sample C2 Dry Mixed Complex Mixing and compounding of comparative dry mix composites and compounds were carried out as described below in Tables 2 and 4-5. The rubber used was standard grade RSS3 natural rubber (Von Bundit Co., Thailand) unless otherwise indicated.
[0174] Sample C1 Preparation of solid elastomer masterbatch C1 Comparative solid elastomer masterbatch sample was prepared according to the liquid masterbatch process of US Pat. No. 8,586,651, Example 2, except as described below.
[0175] The elastomer latex (thinned and desludged MVL Field latex) had a dry rubber content of 28 wt. % and the filler slurry contained 13-14 wt. % carbon black (Vulcan® 7H carbon black (N234 grade) obtained from Cabot Corporation, Boston, MA). The flow rates were adjusted to obtain a target finished carbon black charge of 50 phr at the desired production rate. The average carbon black charge level of the resulting composite was 50.8 phr. The dewatered composite was masticated and mixed with 2 phr of antioxidant (6PPD) in a continuous mixer (Farrel Unimix Continuous Mixer (FCM) equipped with two #15 rotors; Farrel Corporation, Ansonia, CT) and dried, further masticated, cooled and dried in an open mill.
[0176] The resulting solid elastomer masterbatch composite was compounded according to the formulation in Table 3 and the process outlined in Tables 2 and 4.
[0177] Compound Preparation All compound mixing processes were carried out as described in Tables 2 and 4-5 below. A 320 liter cross-reversing mixer (Harburg Feudenberger GK 320) and a 55 liter cross-reversing mixer (Carter 55L with orbiting rotors) were used to mix the composite and compound batches. The first stage mixing for Comparative Examples C1 and C2 was achieved using the 320L mixer, and downstream mixing operations were performed using the 55L mixer. All mixing stages for Inventive Sample E1 were performed using the 55L mixer. The mixing stages were selected to achieve the desired Mooney Viscosity values in the finished compound in the range of 6565-80MU (ML(1+4) at 100°C (373.15K)).
[0178] The first stage mixes of the compounds (C1, E1 and C2 samples) were performed as described in Table 2. [Table 2]
[0179] The moisture content of the extruded composite before curing was measured using a moisture balance (Model: HE53, Manufacturer: Mettler Toledo NA, Ohio). The composite was sliced into small pieces (size: length, width, height <5mm) and 2-2.5g of material was placed on a disposable aluminum disk / plate which was placed in the moisture balance. Weight loss was recorded for 30 minutes at 125°C (398.15K). At the end of the 30 minutes, the moisture content of the composite was recorded as follows: Moisture content of the complex = ((initial weight - final weight) / initial weight) * 100
[0180] The carbon black loading in the composites was determined by thermogravimetric analysis (Model Q500 unit, manufacturer: TA Instruments, DE). Approximately 15-20 mg of rubber sample was used. The sample was first heated at 30°C (303.15 K) / min from room temperature to 125°C (398.15 K) under nitrogen atmosphere, isothermal for 30 minutes to remove moisture, then heated at 30°C (303.15 K) / min up to 550°C (823.15 K) and isothermal for 5 minutes to determine the rubber content. After switching the atmosphere to air, the sample was then heated at 30°C (303.15 K) / min up to 800°C (1073.15 K) and isothermal for 15 minutes to determine the carbon black (CB) content and other residues. The CB loading was then calculated based on the rubber and CB content data.
[0181] The following tests were used to obtain the rubber properties for each of the vulcanized tire treads: - The tensile stress at 100% elongation (M100) and 300% elongation (M300) were evaluated according to ASTM D412 at 23°C (296.15K) (RT) and 50% relative humidity. The loss tangent was measured by dynamic mechanical analysis temperature sweep in tension mode under 0.5% strain at 10Hz with a pre-tension of 0.5N. The results are reported at a temperature of 60°C (333.15K).
[0182] Tread Mixing Procedure Finishing compounds were made with the formulations in Table 3. These formulations were mixed as described in Tables 2 and 4.
[0183] To convert and compound the C2 dry mix composite into a vulcanized tire tread, at least one additional mixing stage was carried out as described in Table 5.
[0184] Ingredients used in all formulations included carbon black filler (Vulcan® 7H (N234) carbon black obtained from Cabot Corporation), antioxidants 6PPD [N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine] and TMQ, standard rubber grades of zinc oxide, stearic acid and sulfur, and TBBS accelerator, all obtained from Akrochem, Akron, Ohio. The solid dried RSS3 natural rubber had a moisture content of <1% by weight. [Table 3] [Table 4] [Table 5]
[0185] Tires made with tread compounds C1, E1 and C2 The manufacture of tires made with the inventive tread compounds and the comparative compounds was carried out by known processes.
[0186] An ORBITREAD® retreading device (McNeil & NRM, Inc., Akron, Ohio) and process was used to build tires (tire size: 195 / 55R15). The tires were built and cured by standard techniques known in the art, including the following steps: (1) a new commercial tire was ground to remove the tread compound; (2) the rubber compound was extruded and applied to the tire; and (3) the strip-applied tire was cured at 150° C. (423.15 K) using pre-determined cure conditions (cure time) based on cure curves, thermocouple measurements of tire temperature profiles, and modeling of tire cure behavior.
[0187] Table 6 lists the tested properties of the cured tire treads of Experimental C1, E1 and C2, along with the same properties measured in a series of 32 comparative commercial tire treads designed for heavy vehicles, e.g., trucks, containing natural rubber and carbon black as the sole rubber and reinforcing fillers, respectively. [Table 6]
[0188] The data in Table 6 demonstrate that tire tread compounds comprising natural rubber and wet carbon black according to the present invention have: (a) higher tensile stress ratio (M300 / M100) and (b) lower δ values than Comparative Example C2 prepared by a dry mix process; and (a) equivalent elongation at break and (b) closer M300 / M100 values to those of Comparative Example C1 prepared by a liquid masterbatch process, while having significant wet mix composite processing advantages gained by eliminating the complexities and limitations of liquid masterbatch.
[0189] The data in Table 6 further demonstrate that the tire treads of the present invention have a combination of: (a) higher elongation to break and, in all but two cases, higher tensile stress ratios (M300 / M100); and (b) lower or comparable tan δ values, as compared to a wide range of commercially available truck tire tread compounds made from natural rubber / carbon black formulations at similar filler loading levels with comparable reinforcing grade carbon black fillers.
[0190] Example 4 Filler dispersion in tread compounds The carbon black filler dispersion in tire treads made with the compounds of Examples 1-3, along with samples of commercial truck tire treads containing comparable rubber formulations, was measured by the following method: Macrodispersion for the vulcanized compounds is designated V, and the area percentage of undispersed carbon black particles greater than 10 μm was determined in the tread samples by optical microscopy in transmission mode.
[0191] Macro Dispersion Test Method: The macrodispersion was characterized by optical microscopy in transmission mode. Cryomicrotome sections (1 μm thick) of the rubber samples were cut with a diamond knife on a PTPC PowerTome ultramicrotome instrument (RMC Boeckeler). The sections were placed on glass slides and cut at 0.55 mm 2 Transmission optical imaging was performed at a resolution of 0.65 μm / pixel with a field of view of 10 μm. At least 10 optical images were acquired for each sample, with each image taken from a different slice of the same sample. The images were first processed by correcting the image non-uniform background with a pseudo flat-field correction based on Gaussian blur. Image noise was reduced using an edge-preserving bilateral filter, and image contrast enhancement was applied if necessary. The dark and light objects in the images represented non-dispersed particles and voids, respectively, while the gray image background represented the rubber areas with well-dispersed carbon black. The objects were separated from the images by image segmentation using a suitable global or local thresholding method to produce two binary images representing non-dispersed particles and voids, respectively. The filtering and segmentation of the images were optimized to ensure that the boundaries of voids and non-dispersed particles were clearly defined by visual comparison between the segmented and original images. The size distribution of the non-dispersed particles was then analyzed from each binary image. The size of the non-dispersed particles was determined using the area-equivalent diameter of the corresponding object in the binary image. The area-equivalent diameter is: Area-equivalent diameter = (4 * (area of dark object / π) 1 / 2As used herein, the term "particles" refers to carbon black agglomerates rather than individual primary particles of carbon black. The area percentage of undispersed carbon black particles greater than 10 μm (value "V") is shown in Table 7. [Table 7]
[0192] In examining the macrodispersion characteristics, Sample C1, the comparative liquid masterbatch sample, has more macrodispersion as indicated by fewer undispersed large particles compared to Sample E1 of the present invention. The tire tread of the present invention had more undispersed large filler particles than the C1 liquid masterbatch sample, but better dispersion and fewer undispersed large filler particles than all of the comparative commercial tread samples. Despite demonstrating slightly less beneficial macrodispersion characteristics compared to Sample C1, which was made by a process known to deliver excellent carbon black macrodispersion and associated excellent rubber material properties to tire treads, Sample E1 of the present invention unexpectedly exhibited rubber properties comparable to those of Sample C1, as indicated by the data set forth in Table 6.
[0193] Consistent with the superior macro-dispersion characteristics of inventive Sample E1 compared to those of comparable commercial tire treads, the rubber material properties of Sample E1 are superior to those of the comparative commercial tread compounds.
[0194] Example 5 Tread compound made from a blend of elastomers and fillers Wet mixed composite preparation In this example, sample E3, a wet mix composite, was prepared using a blend of two elastomers (RSS1 natural rubber from RCMA Group, Singapore and Buna® CB22 butadiene rubber from Lanxess, Germany, at a NR / BR ratio of 80 / 20 phr) and two fillers (PROPEL® X25 carbon black from Cabot Corporation and ZEOSIL® Z1165 MP precipitated silica from Solvay USA Inc., Cranbury, NJ). Two wet mix composites (Part A and Part B) were prepared to make the E3 sample compound. Undried carbon black pellets having a moisture content of 55-58% based on the weight of the total wet carbon black were mixed with natural rubber to make the Part A formulation described in Table 8A. To make the Part B formulation described in Table 8A, Z1165 MP silica (5-7% moisture) was placed in a 5 gallon container and water (treated with reverse osmosis) was slowly added while mixing at variable speed with a Warner Paint agitator attached to an Ika laboratory mixer until the water and silica were homogenous and formed a wet paste. The container of wet silica was sealed for 24 hours and then added to the other ingredients of Part B including the silane (Si69) coupling agent in the preparation of the Part B wet mix composite. [Table 8A]
[0195] A BR-1600 Banbury® laboratory mixer ("BR1600" mixer; Farrel Corporation, Ansonia, CT) was used to make the wet mixed composite parts A and B. The BR1600 mixer was powered by two two-blade tangential rotors (2WL) giving a capacity of 1.6 L. The process used to prepare the two wet mixed composites is shown in Table 8B. [Table 8B]
[0196] Compound Preparation The formulation used for the E3 sample compound is listed in Table 9. The ingredients used included the antioxidant 6PPD [N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine] (also used in Parts A and B) and standard rubber grades of TMQ, zinc oxide, stearic acid, wax beads, sulfur, and TBBS accelerators, all obtained from Akrochem, Akron, Ohio. The solid dry natural rubber had a moisture content of <1% by weight.
[0197] A cross-rotating mixer (Carter 55L cross-rotating mixer with gyratory rotor by Carter, Manchester, UK) was used to mix the E3 sample compound. The mixing process was carried out as described in Table 10.
[0198] Tires with treads containing the E3 sample compound were prepared as described in Examples 1-3. [Table 9] [Table 10] [Table 11]
[0199] As can be observed from the macrodispersion data in Table 7 for the E3 sample tread of the present invention, compared to comparable commercial tire treads, the tire tread of the present invention containing a blend of elastomers and silica and carbon black fillers exhibits higher quality filler dispersion and demonstrates unique product characteristics. The data set forth in Table 11 shows that the rubber properties of such tire treads containing a blend of elastomers and a blend of carbon black and silica fillers were superior to those of a wide range of 13 comparable commercial truck tire treads.
[0200] Applicants specifically incorporate the entire contents of all cited references in this disclosure.Furthermore, when an amount, concentration, or other value or parameter is given as either a range, a preferred range, or a list of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed from any pair of upper range or preferred value and any lower range or preferred value, regardless of whether the ranges are separately disclosed.When a numerical range is recited herein, unless otherwise stated, the range is intended to include its endpoints, as well as all integers and fractions within the range.The scope of the present invention is not intended to be limited to the specific values recited when defining a range.
[0201] Other embodiments of the invention will be apparent to those skilled in the art from consideration of the specification and practice of the invention disclosed herein. It is intended that the specification and examples be considered as examples only, with a true scope and spirit of the invention being indicated by the following claims and equivalents thereof.
Claims
1. 1. A tire tread comprising at least one elastomer and 40 to 80 phr of at least one filler, said filler comprising at least 40 phr of at least one carbon black, said tire tread comprising: a. Elastic modulus ratio > 5.60; b. Percent elongation at break >470; and c. Loss tangent at 60° C. (333.15 K) ≧0.10 and <0.25 The tire tread comprising:
2. 2. The tire tread of claim 1, wherein said modulus ratio, said percent elongation at break, and said loss tangent values are based on said tire tread having said carbon black at 50 phr.
3. 2. The tire tread of claim 1, wherein said elastic modulus ratio is between 5.60 and 6.
30.
4. 2. The tire tread of claim 1, wherein said elastic modulus ratio is between 5.70 and 6.
30.
5. 2. The tire tread of claim 1, wherein said percent elongation at break is between 475 and 550.
6. 2. The tire tread of claim 1, wherein said percent elongation at break is between 480 and 525.
7. 2. The tire tread of claim 1, wherein said percent elongation at break is between 480 and 500.
8. 2. The tire tread of claim 1, wherein said loss tangent is between 0.10 and 0.
22.
9. 2. The tire tread of claim 1, wherein said loss tangent is between 0.12 and 0.
20.
10. 2. The tire tread of claim 1, wherein said elastomer comprises a blend of elastomers selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, and blends thereof.
11. 1. A tire tread comprising at least one elastomer and 20 to 80 phr of at least one filler, said filler comprising up to 40 phr of at least one carbon black, said tread comprising: a) Elastic modulus ratio ≧5.43; b) percent elongation at break >400; and c) Loss tangent at 60° C. (333.15 K) >0.09 and <0.15 The tire tread comprising:
12. 12. The tire tread of claim 11, wherein said elastic modulus ratio, said percent elongation at break, and said loss tangent values are based on said tire tread having said carbon black at 40 phr.
13. The tire tread of claim 11, wherein said elastic modulus ratio is between 5.43 and 6.
25.
14. The tire tread of claim 11, wherein said elastic modulus ratio is between 5.43 and 6.
20.
15. The tire tread of claim 11, wherein said percent elongation at break is between 405 and 550.
16. 12. The tire tread of claim 11, wherein said percent elongation at break is between 425 and 525.
17. The tire tread of claim 11, wherein said percent elongation at break is between 425 and 500.
18. The tire tread of claim 11, wherein said loss tangent is between 0.095 and 0.
14.
19. The tire tread of claim 11, wherein said loss tangent is between 0.10 and 0.
12.
20. 20. Tire tread according to any one of the preceding claims, characterized by a macrodispersion value V, which is the area percentage of undispersed carbon black particles larger than 10 μm, determined by optical microscopy in transmission mode according to the formula: 0.01<V<0.
15.
21. 1. A tire tread comprising at least one elastomer and 20 to 80 phr of at least one filler, said filler comprising at least one carbon black, said tread being characterized by a macrodispersion value V, which is the area percentage of undispersed carbon black particles greater than 10 μm, as determined by optical microscopy in transmission mode according to the formula 0.01<V<0.
15.
22. 22. The tire tread of claim 21, wherein said V is based on said tire tread having said carbon black at 50 phr.
23. 1. A tire tread comprising at least one elastomer and 20 to 80 phr of at least one filler, said filler comprising up to 40 phr of at least one carbon black, said tread being characterized by a macrodispersion value V, the area percentage of undispersed carbon black particles greater than 10 μm, determined by optical microscopy in transmission mode, greater than 0.01, said tread having: a) Elastic modulus ratio ≧5.43; or b) percent elongation at break > 400; or c) Loss tangent at 60°C (333.15K) < 0.25 The tire tread having at least one of:
24. 24. The tire tread of claim 23, wherein said elastic modulus ratio, said percent elongation at break, and said loss tangent values are based on said tire tread having said carbon black at 40 phr.
25. 24. Tire tread according to claim 23, wherein said elastic modulus ratio is between 5.43 and 6.
25.
26. 24. Tire tread according to claim 23, wherein said elastic modulus ratio is between 5.43 and 6.
2.
27. 24. The tire tread of claim 23, wherein said percent elongation at break is between 405 and 550.
28. 24. The tire tread of claim 23, wherein said percent elongation at break is between 425 and 525.
29. 24. The tire tread of claim 23, wherein said percent elongation at break is between 425 and 500.
30. 24. The tire tread of claim 23, wherein said loss tangent is between 0.09 and 0.
22.
31. 24. The tire tread of claim 23, wherein said loss tangent is between 0.10 and 0.
20.
32. 32. Tyre tread according to any one of claims 1 to 31, wherein said filler comprises at least one material selected from carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
33. Tire tread according to any one of the preceding claims, wherein said filler comprises at least one material selected from carbon black, silica, and coated and treated materials thereof.
34. Tyre tread according to any one of the preceding claims, wherein said filler comprises carbon black and silica in a carbon black to silica weight ratio of greater than 2.7:
1.
35. 32. Tyre tread according to any one of claims 1 to 31, wherein said elastomer is chosen from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and blends thereof.
36. Tyre tread according to any one of claims 1 to 31, wherein said elastomer is a styrene-butadiene rubber, a functionalized styrene-butadiene rubber, a polybutadiene rubber, a polyisoprene rubber, an ethylene-propylene rubber, a nitrile rubber, a hydrogenated nitrile rubber, or a blend thereof.
37. Tire tread according to any one of claims 1 to 31, wherein said elastomer is natural rubber or functionalized natural rubber or both.
38. 38. The tire tread of claim 37, wherein said fillers are selected from carbon black, silica, and coated and treated materials thereof.
39. 39. The tire tread according to any one of claims 1 to 38, wherein the tire tread further comprises one or more rubber chemicals selected from antidegradants, processing aids and activators, zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and processing oils.
40. The carbon black has a STSA of 140 m 2 / g.
41. The carbon black has a STSA of >150m 2 / g.
42. The carbon black is 120 m 2 / g ~ 180m 2 A tire tread according to any one of claims 1 to 39 having an STSA of 0.1 / g.
43. The carbon black is 150 m 2 / g ~ 160m 2 A tire tread according to any one of claims 1 to 39 having an STSA of 0.1 / g.
44. 1. A tire tread comprising at least one elastomer and 20 to 80 phr of at least one filler, said filler comprising at least 40 phr of at least one carbon black, said tire tread comprising: a) Elastic modulus ratio >5.60; b) a percent elongation at break >480; and optionally c) Loss tangent at 60°C (333.15K) < 0.25 wherein said tread is characterized by a macrodispersion value V, the area percentage of undispersed carbon black particles larger than 10 μm, determined by optical microscopy in transmission mode, greater than 0.
01.
45. 45. Tire tread according to claim 44, wherein V is greater than 0.
02.
46. 46. A tire tread according to claim 44 or 45, having said loss tangent, said loss tangent at 60°C (333.15K) being ≦0.
20.
47. A tire comprising a tire tread according to any one of claims 1 to 46.
48. 48. The tire of claim 47, selected from truck, tractor, trailer, bus, passenger car, performance car, motorcycle, off-road vehicle, construction equipment vehicle, and aircraft tires.
49. The tire is an off-road vehicle or construction vehicle tire, the tread comprising 60 to 100 phr of an elastomer comprising at least one natural or synthetic polyisoprene, and at least 130 m 2 48. The tire of claim 47 comprising at least 40 phr of filler comprising at least one carbon black having a BET of 1.0 ml / g and a COAN of 115 ml / g or less.
50. 50. The tire of claim 49, wherein said tire is an off-road or construction vehicle tire and said tread further comprises at least one styrene butadiene copolymer, or butadiene polymer, or combinations thereof.
51. The tire is an off-road vehicle or construction vehicle tire, the tread comprising 60 to 100 phr of an elastomer comprising at least one natural or synthetic polyisoprene, and at least 130 m 2 48. The tire of claim 47, comprising at least 40 phr of filler comprising at least one carbon black having a BET of 1.0 ml / g and a COAN of 115 ml / g or less and 5 to 10 phr of at least one silica.
52. The tire is a tire for off-road vehicles or construction machinery vehicles, and the tread is 150 m 2 50. The tire of claim 49, further comprising at least one carbon black having a BET greater than 100 ml / g, an OAN less than 100 ml / g, and a COAN less than 90 ml / g.
53. The tire is a high performance car or motorcycle tire, the tread having 100 phr of an elastomer comprising at least one polymer selected from solution styrene butadiene copolymers and butadiene polymers and combinations thereof, and a 150 to 220 m 2 At least one carbon black having an STSA of 150 to 200 m 2 48. The tire of claim 47, comprising at least 40 phr of filler comprising at least one silica having a BET of 0.15 to 0.5% by mass.
54. The tire is a truck or bus tire, the tread comprising from 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer and at least 115 m 2 48. The tire of claim 47, comprising at least 30 phr of filler comprising at least one carbon black having a STSA of 1.0 ml / g and a COAN of less than 110 ml / g, and 1 to 25 phr of at least one silica filler.
55. The tire is a truck or bus tire, the tread comprising from 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer and at least 115 m 2 55. The tire of claim 54 comprising 45 to 60 phr of a filler comprising at least one carbon black having a STSA of 1.0 ml / g and a COAN of less than 110 ml / g, and 1 to 25 phr of at least one silica filler.
56. The tire is a truck or bus tire, the tread comprising 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer, and 150 m 2 55. The tire of claim 54 comprising at least 30 phr of filler comprising at least one carbon black having a BET greater than 100 ml / g, an OAN less than 100 ml / g, and a COAN less than 90 ml / g, and 1 to 25 phr of at least one silica filler.
57. The tire is a truck or bus tire, the shoulder component of the tread being composed of 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer, and at least 120 m 2 48. The tire of claim 47, comprising at least 40 phr of filler comprising at least one carbon black having a BET of 1.0 ml / g and a COAN of less than 110 ml / g, and 1 to 20 phr of at least one silica filler.
58. The tire is a truck or bus tire, and the shoulder component of the tread comprises 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer, and 150 m 2 58. The tire of claim 57, comprising at least 40 phr of filler comprising at least one carbon black having a BET greater than 100 ml / g, an OAN less than 100 ml / g, and a COAN less than 90 ml / g, and 1 to 25 phr of at least one silica filler.
59. The tread underlayer comprises 60 to 100 phr of at least one natural or synthetic polyisoprene elastomer, polybutadiene elastomer, or a combination thereof; and 2 / g BET and I less than 110g / kg 2 48. The tire of claim 47, comprising at least 40 phr of filler comprising at least one carbon black having a valence.
60. 48. The tire of claim 47, wherein said tread comprises at least 20 phr of filler comprising at least one carbon black selected from surface modified carbon black, oxidized carbon black, multiphase aggregate carbon black, and carbon black having an areal hydrogen content of at least 2000 ppm.
61. A vehicle including a rubber tread adapted to fit and be mounted on a journey, said tread comprising a tire tread according to any one of claims 1 to 46.